All-solid secondary battery

The all-solid-state secondary battery with lithium-containing sulfide-based materials and inert members addresses polysulfide side reactions and structural defects, enhancing cycle characteristics and energy density.

JP2024174855APending Publication Date: 2024-12-17SAMSUNG SDI CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
JP2024091631
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-02-26
Filing Date
2024-06-05
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Secondary batteries using sulfur-based materials face issues such as polysulfide side reactions, disruption of ion and electron transmission paths, and defects in the solid electrolyte layer leading to short circuits and reduced cycle characteristics.

Method used

The all-solid-state secondary battery incorporates a positive electrode layer with a lithium-containing sulfide-based active material, a solid electrolyte layer, and a negative electrode layer, with specific capacity ratios and inert members to suppress side reactions and defects, ensuring stable ion and electron transport.

Benefits of technology

This configuration enhances the battery's cycle characteristics by preventing short circuits and improving energy density while maintaining structural integrity during charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024174855000001_ABST
    Figure 2024174855000001_ABST
Patent Text Reader

Abstract

To provide an all-solid secondary battery.SOLUTION: An all-solid secondary battery contains: a positive electrode layer; a negative electrode layer; and a solid electrolyte layer arranged to between the positive electrode layer and the negative electrode layer. The positive electrode layer contains a positive electrode collector and a positive electrode active material layer arranged onto one surface or both surfaces of the positive electrode collector. The positive electrode active material layer contains a lithium-containing sulfide-based positive electrode active material. The lithium-containing sulfide-based positive electrode active material contains a Li2S and Li2S-containing composite body, or a combination of them, and contains a first inactive member arranged onto the one side surface of the positive electrode layer. The negative electrode layer contains: a negative electrode collector; and a first negative electrode active material arranged onto the one surface of the negative electrode collector.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an all-solid-state secondary battery. [Background technology]

[0002] In recent years, with the rapid spread of electronic devices that use batteries, such as mobile phones, notebook computers, and electric vehicles, the demand for secondary batteries with high energy density and large capacity is rapidly increasing. As a result, research and development to improve the performance of lithium secondary batteries is actively underway. A lithium secondary battery is a battery that includes a positive electrode and a negative electrode containing active materials capable of intercalating and deintercalating lithium ions, and an electrolyte. A lithium secondary battery produces electrical energy by oxidation and reduction reactions when lithium ions are intercalated and deintercalated in / from the positive electrode and negative electrode.

[0003] In recent years, industrial demand has led to active development of batteries with high energy density and safety. For example, lithium batteries are used not only in the fields of information-related devices and communication devices, but also in the field of automobiles. In the field of automobiles, safety is particularly important because batteries are related to life.

[0004] Lithium batteries use an electrolyte solution containing a flammable organic solvent, so if a short circuit occurs, there is a risk of overheating and fire.

[0005] All-solid-state batteries that use a solid electrolyte instead of a liquid electrolyte have been proposed.

[0006] Because solid-state batteries do not use flammable organic solvents, the possibility of fire or explosion can be greatly reduced even if a short circuit occurs, making such solid-state batteries significantly safer than lithium batteries that use electrolytes. Summary of the Invention [Problem to be solved by the invention]

[0007] In order to increase capacity, secondary batteries use sulfur-based materials (e.g., S) as positive electrode active materials. Polysulfides are generated from the sulfur-based materials during the charge and discharge process of the secondary battery, and the generated polysulfides move to the negative electrode and react with the negative electrode. Such side reactions reduce the life characteristics of the secondary battery. There is a demand for secondary batteries that can suppress the side reactions between polysulfides and lithium metal.

[0008] In secondary batteries containing sulfur-based materials (e.g., S), the volume of the sulfur-based material increases during initial discharge and then decreases again during charging. As the volume of the sulfur-based material increases, the ion and / or electron transport pathways in the electrode may be interrupted. Such interruption of the ion and / or electron transport pathways causes deterioration of the secondary battery. There is a demand for a secondary battery that can suppress the interruption of such ion and / or electron transport pathways.

[0009] During the manufacturing process and / or the charge / discharge process of a secondary battery, defects occur in the solid electrolyte layer, and cracks occur and grow in the solid electrolyte layer from the defects. Lithium grows through the cracks, causing a short circuit. There is a demand for a secondary battery that can suppress the occurrence of such defects during the manufacturing process and / or the charge / discharge process of the secondary battery.

[0010] The problem to be solved by the present invention is to provide a secondary battery with a novel structure that prevents side reactions between an electrolyte layer and lithium metal during charging and discharging, suppresses interruption of ion and / or electron transport pathways, prevents side reactions caused by polysulfides during charging and discharging, and suppresses the occurrence of defects in the secondary battery during production and / or charging and discharging. [Means for solving the problem]

[0011] According to one embodiment, the present invention includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer disposed on one or both sides of the positive electrode current collector, the positive electrode active material layer includes a lithium-containing sulfide-based positive electrode active material, and the lithium-containing sulfide-based positive electrode active material is Li 2 S., Li 2 a first inactive member disposed on one side of the positive electrode layer, the negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer disposed on one side of the negative electrode current collector, the ratio (B / A) of an initial charge capacity (B) of the first negative electrode active material layer to an initial charge capacity (A) of the positive electrode active material layer is 0.005 to 0.45, and the initial charge capacity of the positive electrode active material layer is greater than a first open circuit voltage (1 st From open circuit voltage, Li / Li + The initial charge capacity of the negative electrode active material layer is determined by charging the negative electrode active material layer to a maximum charging voltage with respect to a second open circuit voltage (2 nd From open circuit voltage, Li / Li + An all-solid-state secondary battery is provided, which is determined by charging to 0.01 V with respect to the positive electrode potential.

[0012] a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer disposed on one or both sides of the positive electrode current collector, the positive electrode active material layer includes a lithium-containing sulfide-based positive electrode active material, and the lithium-containing sulfide-based positive electrode active material is Li 2 The Li 2 S-containing complexes are Li 2 S and lithium salt complex, Li 2 S, lithium salt and conductive material composite, Li 2 S and metal halide complexes, Li 2 S, metal halide and conductive material complex, Li 2 S, lithium salt and metal halide complex, Li 2An all-solid-state secondary battery is provided, comprising a composite of S, a lithium salt, a metal halide, and a conductive material, or a combination thereof, wherein the negative electrode layer comprises a negative electrode current collector and a first negative electrode active material layer disposed on one surface of the negative electrode current collector. Effect of the Invention

[0013] According to the all-solid-state secondary battery having the novel structure of the present invention, it is possible to provide an all-solid-state secondary battery in which short circuits are suppressed and cycle characteristics are improved. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an exemplary embodiment. [Diagram 2] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an exemplary embodiment. [Diagram 3] FIG. 1 is a cross-sectional view of a bi-cell all-solid-state secondary battery according to an exemplary embodiment. [Figure 4] FIG. 2 is a schematic diagram of an all-solid-state secondary battery positive electrode layer according to an exemplary embodiment. [Diagram 5] FIG. 1 is a schematic diagram partially illustrating the inside of an all-solid-state secondary battery according to an exemplary embodiment. [Figure 6] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an exemplary embodiment. [Figure 7] FIG. 1 is a cross-sectional view of an all-solid-state secondary battery according to an exemplary embodiment. [Figure 8] FIG. 1 is a cross-sectional view of a bi-cell all-solid-state secondary battery according to an exemplary embodiment. [Figure 9] FIG. 1 is a cross-sectional view of a stacked bi-cell all-solid-state secondary battery stack according to an exemplary embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Various embodiments are illustrated in the accompanying drawings. However, the concept of the present invention may be embodied in various other forms and should not be construed as being limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the inventive concept to those skilled in the art. The same reference numerals refer to the same components.

[0016] It will be understood that when an element is referred to as being "on" another element, it may be directly on top of the other element, or there may be other elements intervening between them. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements between them.

[0017] Terms such as "first", "second", "third" and the like may be used herein to describe various components, components, regions, layers and / or sections, but these components, components, regions, layers and / or sections should not be limited by these terms. These terms are used only to distinguish one component, component, region, layer or section from another component, component, region, layer or section. Thus, a first component, component, region, layer or section described below can be referred to as a second component, component, region, layer or section without departing from the teachings of this specification.

[0018] The terms used in this specification are intended to describe only certain embodiments and are not intended to limit the inventive concept of the present invention. As used in this specification, the singular form includes the plural form, including "at least one," unless the context clearly dictates otherwise. "At least one" should not be interpreted as being limited to the singular. As used in this specification, the term "and / or" includes any and all combinations of one or more of the listed items. The terms "comprises" and / or "comprising" used in the detailed description specify the presence of the stated features, regions, integers, steps, operations, components, ingredients, and / or components, and do not exclude the presence or addition of one or more other features, regions, integers, steps, operations, components, ingredients, and / or groups thereof.

[0019] Here, spatially relative terms such as "below," "lower," "bottom," "top," "upper," and "top" can be used to easily describe the relationship of one component or feature to another. It will be understood that the spatially relative terms are intended to include different orientations of the device when used or operated in addition to the orientation shown. For example, if the device in the drawings were turned upside down, a component described as "below" or "below" the other component or feature would be oriented "above" the other component or feature. Thus, the exemplary term "below" can encompass both an up and down orientation. The device could be otherwise oriented (rotated 90 degrees or in another orientation) and the spatially relative terms used herein could be interpreted accordingly.

[0020] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which this disclosure belongs. In addition, terms as defined in commonly used dictionaries should be interpreted to have a meaning consistent with their meaning in the context of the relevant art and this disclosure, and should not be interpreted in an idealized or overly formal sense.

[0021] The embodiments are described herein with reference to cross-sectional views that are schematic illustrations of idealized embodiments. As such, variations from the shapes of the illustrations are to be expected as a result of, for example, manufacturing techniques and / or tolerances. Thus, the embodiments described herein should not be construed as limited to the particular shapes of the regions as illustrated herein, but should include, for example, deviations in shapes resulting from manufacturing. For example, a region illustrated or described as flat can typically have rough and / or non-linear characteristics. Additionally, corners illustrated as sharp may be rounded. Thus, the illustrated regions are schematic in nature, and the shapes are not intended to illustrate the exact shapes of the regions, and are not intended to limit the scope of the claims.

[0022] "Group" means a group of the Periodic Table of the Elements according to the International Union of Pure and Applied Chemistry ("IUPAC") Group 1-18 classification system.

[0023] Unless otherwise defined in this specification, the particle size may be the average particle size. Also, the particle size refers to the average particle size (D50), which means the particle size at which the cumulative volume in the particle size distribution is 50% by volume. The average particle size (D50) may be measured by a method widely known to those skilled in the art, for example, by measuring with a particle size analyzer, or by measuring with a transmission electron microscope or a scanning electron microscope. As another method, the average particle size (D50) value may be obtained by measuring with a measuring device using a dynamic light-scattering method, performing data analysis to count the number of particles for each particle size range, and then calculating the average particle size (D50) value. Alternatively, the average particle size (D50) may be measured using a laser diffraction method. When measuring by the laser diffraction method, more specifically, the particles to be measured are dispersed in a dispersion medium, then introduced into a commercially available laser diffraction particle size measuring device (e.g., MT3000 by Microtrac) and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and the average particle size (D50) based on the 50% standard of the particle size distribution in the measuring device can be calculated. The "average particle size" is, for example, D50, which is the median particle size.

[0024] D50 is a particle size corresponding to 50% cumulative volume calculated from the particle side having a small particle size in the particle size distribution measured by a laser diffraction method.

[0025] D90 is the particle size corresponding to 90% cumulative volume calculated from the particle side having a small particle size in the particle size distribution measured by a laser diffraction method.

[0026] D10 is a particle size corresponding to 10% cumulative volume calculated from the particle side having a small particle size in the particle size distribution measured by a laser diffraction method.

[0027] In this disclosure, "metal" includes both metals and metalloids such as silicon and germanium, in either the elemental or ionic state.

[0028] In this disclosure, "alloy" means a mixture of two or more metals.

[0029] In this disclosure, "electrode active material" refers to an electrode material that can undergo lithiation and delithiation.

[0030] In this disclosure, "positive electrode active material" refers to a positive electrode material that can undergo lithiation and delithiation.

[0031] In this disclosure, "negative electrode active material" refers to a negative electrode material that can undergo lithiation and delithiation.

[0032] As used herein, "lithiation" and "lithiating" refer to the process of adding lithium to an electrode active material.

[0033] As used herein, "delithiation" and "delithiating" refer to the process of removing lithium from an electrode active material.

[0034] In this disclosure, "charge" and "charging" refer to the process of providing electrochemical energy to a battery.

[0035] In this disclosure, "discharge" and "discharging" refer to the process of removing electrochemical energy from a battery.

[0036] In this disclosure, "positive electrode" and "cathode" refer to the electrodes where electrochemical reduction and lithiation occurs during the discharge process.

[0037] In this disclosure, "negative electrode" and "anode" refer to the electrodes where electrochemical oxidation and delithiation occurs during the discharge process.

[0038] While particular embodiments have been described above, presently unforeseen or unanticipated alternatives, modifications, variations, improvements, and substantial equivalents may occur to the applicant or those skilled in the art. Accordingly, the appended claims as filed and as they may be amended are intended to include all such alternatives, modifications, variations, improvements, and substantial equivalents.

[0039] Hereinafter, the all-solid-state secondary battery according to the exemplary embodiment will be described in further detail.

[0040] [All-solid-state secondary battery] An all-solid-state secondary battery according to one embodiment includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer disposed on one or both sides of the positive electrode current collector, the positive electrode active material layer includes a lithium-containing sulfide-based positive electrode active material, and the lithium-containing sulfide-based positive electrode active material is Li 2 S., Li 2 a first inactive member disposed on one side of the positive electrode layer, the negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer disposed on one side of the negative electrode current collector, the ratio (B / A) of an initial charge capacity (B) of the first negative electrode active material layer to an initial charge capacity (A) of the positive electrode active material layer is 0.005 to 0.45, and the initial charge capacity of the positive electrode active material layer is greater than a first open circuit voltage (1 st From open circuit voltage, Li / Li + The initial charge capacity of the negative electrode active material layer is determined by charging the negative electrode active material layer to a maximum charging voltage with respect to a second open circuit voltage (2 nd From the open circuit voltage, Li / Li + It is determined by charging to 0.01V against

[0041] The all-solid-state secondary battery contains a lithium-containing sulfide-based positive electrode active material instead of lithium metal as a lithium source. This allows the omission of a lithium source such as lithium metal in the anode layer. The volume of the anode layer is reduced, thereby improving the energy density of the all-solid-state secondary battery.

[0042] The all-solid-state secondary battery contains a lithium-containing sulfide-based positive electrode active material as a positive electrode active material. Therefore, the disconnection of the ion and / or electron transport pathway caused by the volume increase during initial discharge of the non-lithium-containing sulfide-based positive electrode active material, for example, sulfur (S), is prevented. By preventing such disconnection of the ion and / or electron transport pathway, the cycle characteristics of the all-solid-state secondary battery are improved.

[0043] The all-solid-state secondary battery includes a first negative electrode active material layer having an initial charge capacity in the range of 0.005 to 0.45 compared to the initial charge capacity of the positive electrode active material layer. Since the first negative electrode active material layer has a small initial charge capacity in such a range, the negative electrode layer can effectively compensate for the volume change of the positive electrode layer during charging and discharging. As a result, the overall volume change of the all-solid-state secondary battery is suppressed during charging and discharging. Since deterioration such as crack generation due to a sudden volume change during charging and discharging of the all-solid-state secondary battery is prevented, a short circuit of the all-solid-state secondary battery is prevented and the cycle characteristics are improved.

[0044] The solid electrolyte layer in the all-solid-state secondary battery prevents polysulfides generated during charging and discharging of the lithium-containing sulfide-based positive electrode active material from migrating to the negative electrode layer, thereby suppressing side reactions between the polysulfides and the negative electrode active material.

[0045] By disposing an inactive member on one side of the positive electrode layer, cracks in the solid electrolyte layer that occur when the all-solid-state secondary battery is pressurized and / or when it is charged and discharged are suppressed. Therefore, cracks in the solid electrolyte layer are suppressed during the manufacture of the all-solid-state secondary battery and / or during charging and discharging, and thus short-circuiting of the all-solid-state secondary battery is suppressed. As a result, short-circuiting of the all-solid-state secondary battery is prevented, and the life characteristics are improved.

[0046] 1 to 9, the all-solid-state secondary battery 1 includes a positive electrode layer 10, a negative electrode layer 20, and a solid electrolyte layer 30 disposed between the positive electrode layer 10 and the negative electrode layer 20. The positive electrode layer 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on one or both sides of the positive electrode current collector. The positive electrode active material layer 12 includes a sulfide-based positive electrode active material, and the sulfide-based positive electrode active material is Li 2 S., Li 2 The positive electrode layer 10 includes a first inactive member 40 disposed on one side thereof. The negative electrode layer 20 includes a negative electrode current collector 21 and a first negative electrode active material layer 22 disposed on one side thereof. The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer 22 to the initial charge capacity (A) of the positive electrode active material layer 12 is 0.005 to 0.45. The initial charge capacity of the positive electrode active material layer 12 is calculated from the first open circuit voltage as follows: Li / Li + The initial charge capacity of the first negative electrode active material layer 22 is determined by charging the first negative electrode active material layer 22 to a maximum charging voltage (2 nd From the open circuit voltage, Li / Li + It is determined by charging to 0.01 V versus current. The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer 22 to the initial charge capacity (A) of the positive electrode active material layer 12 is, for example, 0.01 to 0.4, 0.01 to 0.3, 0.01 to 0.2, or 0.01 to 0.1.

[0047] [Positive electrode layer] [Cathode layer: Cathode active material] 1 to 9, the positive electrode active material layer 12 includes, for example, a positive electrode active material and a solid electrolyte. The solid electrolyte included in the positive electrode active material layer 12 may be similar to or different from the solid electrolyte included in the solid electrolyte layer 30. For details about the solid electrolyte, please refer to the section on the solid electrolyte layer 30.

[0048] The positive electrode active material includes a lithium-containing sulfide-based positive electrode active material. The lithium-containing sulfide-based positive electrode active material is, for example, an electrode material in which lithium is added to a sulfur-based positive electrode active material. The sulfur-based positive electrode active material includes, for example, a sulfur-based material, a sulfur-based material-containing composite, or a combination thereof. The sulfur-based material includes, for example, inorganic sulfur, Li 2 S n (n>1), disulfide compounds, organic sulfur compounds, carbon-sulfur polymers, or combinations thereof. The sulfur-based material-containing composite may be inorganic sulfur, Li 2 S n (n>1), a disulfide compound, an organic sulfur compound, a carbon-sulfur polymer, or a composite containing a combination thereof. The sulfur-based material-containing composite may include, for example, a composite of a sulfur-based material and carbon, a composite of a sulfur-based material and carbon and a solid electrolyte, a composite of a sulfur-based material and carbon and a lithium salt, a composite of a sulfur-based material and a lithium salt, a composite of a sulfur-based material and a solid electrolyte, a composite of a sulfur-based material and a metal carbide, a composite of a sulfur-based material and carbon and a metal carbide, a composite of a sulfur-based material and a metal nitride, a composite of a sulfur-based material and carbon and a metal nitride, or a combination thereof. The lithium-containing sulfide-based positive electrode active material provides a higher discharge capacity per unit weight than an oxide-based positive electrode active material, and therefore the energy density per unit weight of an all-solid-state secondary battery containing the lithium-containing sulfide-based positive electrode active material can be improved.

[0049] The lithium-containing sulfide-based positive electrode active material is, for example, Li 2 S., Li 2 Lithium-containing sulfide-based positive electrode active materials with high capacity include S-containing complexes or combinations thereof. 2 S., Li 2By including the S-containing complex or a combination thereof, the use of lithium metal can be omitted when manufacturing an all-solid-state secondary battery. Lithium metal has high reactivity and high ductility, which may reduce mass productivity during battery manufacturing. Therefore, mass productivity of the all-solid-state secondary battery can be improved. The omission of lithium metal in the anode layer reduces the volume of the anode layer, thereby improving the energy density per unit volume of the all-solid-state secondary battery, and an all-solid-state secondary battery with a simpler structure can be constructed.

[0050] Lithium-containing sulfide-based positive electrode active material (e.g., Li 2 S) undergoes delithiation during initial charging, for example, and its volume decreases, and during subsequent discharging, its volume increases again due to lithiation. Therefore, the volume of the lithium-containing sulfide-based positive electrode active material changes while maintaining the ion and / or electron transfer path due to the conductive material, etc., disposed around the lithium-containing sulfide-based positive electrode active material, so that the ion and / or electron transfer path is unlikely to be interrupted. In contrast, the sulfur-based positive electrode active material (e.g., S) undergoes lithiation during initial discharging, for example, and its volume decreases again due to delithiation during subsequent charging. Therefore, the initial ion and / or electron transfer path due to the conductive material, etc., disposed around the sulfur-based positive electrode active material may collapse due to the initial volume increase of the sulfur-based positive electrode active material, so that the ion and / or electron transfer path is likely to be interrupted.

[0051] The particle size of the lithium-containing sulfide-based positive electrode active material may be, for example, 1 nm to 50 μm, 10 nm to 50 μm, 50 nm to 40 μm, 100 nm to 30 μm, 500 nm to 30 μm, or 1 μm to 20 μm. When the lithium-containing sulfide-based positive electrode active material has a particle size in such a range, the cycle characteristics of the all-solid-state secondary battery containing the lithium sulfide-based positive electrode active material can be further improved. 2 S-containing complexes include, for example, Li 2 It is a composite of S and a conductive material.

[0052] The conductive material may be, for example, an ionically conductive material, an electronically conductive material, or a combination thereof.

[0053] The electronic conductivity of the electronic conductive material is, for example, 1.0×10 3 S / m, 1.0×10 4 S / m, or 1.0×10 5 S / m or more. The form of the electronically conductive material is, for example, but not limited to, a particulate electronically conductive material, a plate-shaped electronically conductive material, a rod-shaped electronically conductive material, or a combination thereof. The electronically conductive material may be, for example, carbon, a metal powder, a metal compound, or the like. When carbon is included as the electronically conductive material, since carbon has high electronic conductivity and is light, it is possible to realize an all-solid-state secondary battery having a high energy density per unit mass. The electronically conductive material may have pores.

[0054] The electron-conducting material has pores, which allows Li 2 Contains S in the pores and Li 2 Increase the contact area between S and the electronic conductive material, and Li 2 The specific surface area of ​​S can be increased. The pore volume is, for example, 0.1 cc / g to 20.0 cc / g, 0.5 cc / g to 10 cc / g, or 0.5 cc / g to 5 cc / g. The average pore diameter is, for example, 1 nm to 100 nm, 1 nm to 50 nm, or 1 nm to 20 nm. The BET specific surface area of ​​the electron conductive material having pores is 200 m or more when the average pore diameter is 15 nm or less. 2 / g~4500m 2 / g, and if the average pore size is greater than 15 nm, 2 / g~2500m 2 The BET specific surface area, pore size, pore volume and average pore size can be determined using nitrogen adsorption methods such as ASTM D6556, ASTM D4567, ISO 9277:2022, etc.

[0055] The ionic conductivity of the ion-conductive material is, for example, 1.0×10 -5 S / m, 1.0×10 -4 S / m, or 1.0×10-3 The ion conductive material may have pores. By having pores, Li 2 Contains S in the pores and Li 2 The contact area between S and the ion-conducting material is increased, and Li 2 The specific surface area of ​​S can be increased. The form of the ion conductive material is, for example, a particulate ion conductive material, a plate-shaped electronic conductive material, a rod-shaped electronic conductive material, or a combination thereof, but is not necessarily limited thereto. The ion conductive material may be, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, or the like. When the ion conductive material includes a sulfide-based solid electrolyte, the sulfide-based solid electrolyte has high ion conductivity and can be formed into various shapes, so that an all-solid-state secondary battery having a large capacity can be realized.

[0056] Li 2 S-containing complexes include, for example, Li 2 S and conductive material composite, Li 2 S, solid electrolyte, and conductive material composite, Li 2 S and solid electrolyte composite, Li 2 S, lithium salt and conductive material composite, Li 2 S complex with lithium salt, Li 2 S, lithium salt and conductive material composite, Li 2 S complex with lithium salt, Li 2 S and metal carbide complex, Li 2 S, metal carbide and conductive material composite, Li 2 S and metal nitride complexes, Li 2 Composites of S, metal nitrides, conductive materials, or combinations thereof. 2 The S-containing complex is Li 2 It is distinguished from simple mixtures of S and conductive materials such as solid electrolytes, lithium salts, metal carbides, and metal nitrides. 2 Simple mixtures of S with conductive materials, solid electrolytes, lithium salts, metal carbides, metal nitrides, etc. 2By not maintaining a dense interface between S and other components, high interfacial resistance is provided, which can result in a decrease in the life characteristics of the all-solid-state secondary battery.

[0057] Li 2 The S-containing complex is Li 2 S-containing complexes include, for example, Li 2 S complex with lithium salt, Li 2 S, lithium salt and conductive material composite, Li 2 S complex with metal halides, Li 2 S, metal halide and conductive material composite, Li 2 S, lithium salt and metal halide complex, Li 2 The lithium salt may include a complex of S, a lithium salt, a metal halide, a conductive material, or a combination thereof. 2 The S-containing complex is Li 2 It is distinguished from simple mixtures of S with lithium salts, metal halides, conductive materials, etc. 2 Simple mixtures of S with metal halides, lithium salts, conductive materials, etc., are Li 2 The inability to maintain a dense interface between S and the other components may result in high interfacial resistance, which may result in reduced life characteristics of the all-solid-state secondary battery. 2 S-containing complexes are Li 2 Contains S.

[0058] Li 2 Since S has a high theoretical capacity, it is possible to provide a secondary battery with a high energy density. 2 Since S has low ionic and / or electronic conductivity, in order to overcome this drawback, it is used to form a complex with lithium salt, metal halide, conductive material, etc. 2 Li in S-containing complexes 2 The S content is, for example, Li 2 The amount of S may be 10 to 80 wt%, 20 to 80 wt%, 30 to 80 wt%, or 40 to 80 wt% of the total weight of the S-containing composite. 2 Li in S-containing complexes 2 If the S content increases excessively, Li2 It is not easy to improve the ionic and / or electronic conductivity of S-containing composites. 2 Li in S-containing complexes 2 If the S content is too low, the energy density of the all-solid-state secondary battery may decrease.

[0059] Li 2 The composite of S and a conductive material includes a conductive material. The conductive material includes, for example, a carbon-based material. Any carbon-based material that is used as a conductive material in the art as a material containing carbon atoms can be used. The carbon-based material may be, for example, a crystalline carbon-based material, an amorphous carbon-based material, or a combination thereof. The carbon-based material may be, for example, a calcined product of a carbon precursor. The carbon-based material may be, for example, a carbon nanostructure. The carbon nanostructure may be, for example, a one-dimensional carbon nanostructure, a two-dimensional carbon nanostructure, a three-dimensional carbon nanostructure, or a combination thereof. The carbon nanostructure may be, for example, a carbon nanotube, a carbon nanofiber, a carbon nanobelt, a carbon nanorod, graphene, or a combination thereof. The carbon-based material may be, for example, a porous carbon-based material or a non-porous carbon-based material. The porous carbon-based material may include, for example, periodic and regular two-dimensional or three-dimensional pores. The porous carbon-based material may be, for example, carbon black such as Ketjen Black, Acetylene Black, Denka Black, Thermal Black, Channel Black, graphite, activated carbon, or a combination thereof. The form of the carbon-based material may be, for example, particulate, sheet, flake, or the like, but is not limited thereto, and any form used as a carbon-based material in the art may be used. 2 The method for producing the composite of S and carbon-based material may be, but is not limited to, a dry method, a wet method, or a combination thereof. 2 Methods for producing a composite of S and a carbon-based material include, for example, milling, heat treatment, vapor deposition, etc., but are not necessarily limited to these, and any method used in the art can be used.

[0060] Li 2 The composite of S, a solid electrolyte, and a conductive material includes a conductive material and a solid electrolyte. The conductive material includes, for example, a carbon-based material. The carbon-based material is the above-mentioned Li 2 The carbon-based material used in the composite of S and the carbon-based material is referred to. The solid electrolyte can be, for example, any material used as an ion-conducting material in the art. The solid electrolyte can be, for example, an inorganic solid electrolyte. The solid electrolyte can be, for example, a crystalline solid electrolyte, an amorphous solid electrolyte, or a combination thereof. The solid electrolyte can be, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, or a combination thereof. The sulfide-based solid electrolyte can include, for example, Li, S, and P, and can further include a halogen element selectively. The sulfide-based solid electrolyte can be selected from the sulfide-based solid electrolytes used in the solid electrolyte layer. The sulfide-based solid electrolyte can be, for example, a sulfide-based solid electrolyte having a solubility of 1×10- at room temperature. 5 The oxide-based solid electrolyte has an ionic conductivity of 1×10-2000 S / cm or more at room temperature. The oxide-based solid electrolyte contains, for example, Li, O, and a transition metal element, and may further contain other elements selectively. 5 The solid electrolyte may have an ion conductivity of at least 10 S / cm. The oxide-based solid electrolyte may be selected from among the oxide-based solid electrolytes used in the solid electrolyte layer.

[0061] Li 2 The composite of S and a solid electrolyte includes a solid electrolyte. The solid electrolyte is the above-mentioned Li 2 Refers to the solid electrolyte used in the composite of S, conductive material and solid electrolyte. Li 2 The composite of S, lithium salt and conductive material is Li 2 The conductive material includes, for example, a carbon-based material. The carbon-based material includes the Li 2The term "lithium salt" refers to a carbon-based material used in a composite of S and a conductive material. The lithium salt is a compound that does not contain sulfur (S). The lithium salt may be, for example, a binary compound or a ternary compound. The lithium salt may be, for example, a binary compound consisting of lithium and one element selected from Groups 13 to 17 of the periodic table. The binary compound may be, for example, LiF, LiCl, LiBr, LiI, LiH, Li 2 O, Li 2 Se, Li 2 Te, Li 3 N, Li 3 P, Li 3 As, Li 3 Sb, Li 3 Al 2 and LiB 3 The lithium salt may be, for example, a ternary compound consisting of lithium and two elements selected from groups 13 to 17 of the periodic table. The ternary compound may be, for example, Li 3 OCl, LiPF 6 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiClO 4 , LiAlO 2 , LiAlCl 4 , LiNO 3 , Li 2 CO 3 , LiBH 4 , Li 3 BO 3 , Li 3 PO 4 , Li 4 NCl, Li 5 NCl 2 and Li 3 BN 2 The lithium salts include one or more lithium halide compounds selected in particular from LiF, LiCl, LiBr, and LiI. 2 A composite of S, a lithium salt, and a conductive material is, for example, Li 2A composite of S, lithium halide, and a carbon-based material may also be used. 2 By further including a lithium halide compound in the composite of S, a lithium salt, and a carbon-based material, it is possible to provide further improved ionic conductivity. 2 The composite of S, lithium salt, and carbon-based material is Li 2 It is distinguished from simple mixtures of S, lithium salts, and carbon-based materials. 2 A simple mixture of S, a lithium salt, and a carbon-based material is Li 2 Since it is not possible to maintain a dense interface between S, the lithium salt, and the carbon-based material, this may provide high interfacial resistance, which may result in a decrease in the life characteristics of the all-solid-state secondary battery.

[0062] Li 2 The complex of S and a lithium salt contains a lithium salt. The lithium salt is the above-mentioned Li 2 S refers to the lithium salt used in the composite of lithium salt and conductive material.

[0063] Li 2 The complex of S and a metal carbide includes a metal carbide. The metal carbide is, for example, a two-dimensional metal carbide. The two-dimensional metal carbide is, for example, M n+1 C n T x (M is a transition metal, T is an end group, T is O, OH and / or F, n=1, 2 or 3, x is the number of end groups). Two-dimensional metal carbides are, for example, Ti 2 CT x , (Ti 0.5 , Nb 0.5 ) 2 CT x , Nb 2 CT x , V 2 CT x , Ti 3 C 2 T x , (V 0.5 , Cr 0.5 ) 3 C 2 T x , Ti 3 CNTx , Ta 4 C 3 T x , Nb 4 C 3 T x or a combination thereof. The surface of the two-dimensional metal carbide is terminated with O, OH and / or F. The total number of O, OH and F groups on the surface is the number of terminal groups.

[0064] Li 2 The composite of S, metal carbide and conductive material is Li 2 The conductive material includes S, a metal carbide, and a conductive material. The conductive material includes, for example, a carbon-based material. The carbon-based material includes the above-mentioned Li 2 Refer to the carbon-based materials used in the composite of S and conductive materials. Metal carbides are the same as the Li 2 Reference is made to the metal carbide contemplated in the composite of S and the metal carbide.

[0065] Li 2 The complex of S with metal nitrides is Li 2 S and metal nitrides. Metal nitrides are, for example, two-dimensional metal nitrides. Two-dimensional metal nitrides are, for example, M n+1 N n T x (M is a transition metal, T is an end group, T is O, OH and / or F, n=1, 2 or 3, and x is the number of end groups). The surface of the 2D metal nitride is terminated with O, OH and / or F. The total number of O, OH and F groups on the surface is the number of end groups.

[0066] Li 2 The composite of S, metal nitride and conductive material is Li 2 The conductive material includes S, a metal nitride, and a conductive material. The conductive material includes, for example, a carbon-based material. The carbon-based material includes the above-mentioned Li 2 The carbon-based material used in the composite of S and conductive materials is the Li 2 Refer to the metal nitride used in the composite of S and metal nitride.

[0067] Li2 S and lithium salts (Li a X1 b ) complexes with Li 2 S-Li a X1 b (1≦a≦5, 1≦b≦5), where X1 is I, Br, Cl, F, H, O, Se, Te, N, P, As, Sb, Al, B, OCl, PF 6 , B.F. 4 , SbF 6 , AsF 6 , ClO 4 , AlO 2 , AlCl 4 , NO 3 , CO 3 , B.H. 4 , S.O. 4 , B.O. 3 , P.O. 4 , NCl, NCl 2 , B.N. 2 or a combination thereof.

[0068] Li 2 S and lithium salts (Li a X1 b The composite of (C) and the conductive material (C) is, for example, Li 2 S-Li a X1 b -C (1≦a≦5, 1≦b≦5), where X1 is I, Br, Cl, F, H, O, Se, Te, N, P, As, Sb, Al, B, OCl, PF 6 , B.F. 4 , SbF 6 , AsF 6 , ClO 4 , AlO 2 , AlCl 4 , NO 3 , CO 3 , B.H. 4 , S.O. 4 , B.O. 3 , P.O. 4 , NCl, NCl 2 , B.N. 2 or a combination thereof. The conductive material is, for example, a carbon-based material.

[0069] Li 2S and metal halides (M c X2 d ) complexes, for example, Li 2 S.M. c X2 d -C (1≦c≦5, 1≦d≦5), M is one or more metals selected from Groups 2 to 15 of the Periodic Table, and X2 is I, Br, Cl, F, or a combination thereof. The conductive material is, for example, a carbon-based material.

[0070] Li 2 S and metal halides (M c X2 d The composite of (C) and the conductive material (C) is, for example, Li 2 S.M. c X2 d -C (1≦c≦5, 1≦d≦5), M is one or more metals selected from Groups 2 to 15 of the Periodic Table, and X2 is I, Br, Cl, F, or a combination thereof. The conductive material is, for example, a carbon-based material.

[0071] Li 2 S and lithium salts (Li a X1 b ) and metal halides (M a X2 b ) is a complex with Li 2 S-Li a X1 b -M c X2 d (1≦a≦5, 1≦b≦5, 1≦c≦5, 1≦d≦5), where X1 is I, Br, Cl, F, H, O, Se, Te, N, P, As, Sb, Al, B, OCl, PF 6 , B.F. 4 , SbF 6 , AsF 6 , ClO 4 , AlO 2 , AlCl 4 , NO 3 , CO 3 , B.H. 4 , S.O. 4 , B.O. 3 , P.O. 4 , NCl, NCl2 , B.N. 2 or a combination thereof, wherein M is one or more metals selected from Groups 2 to 15 of the Periodic Table, and X2 is I, Br, Cl, F, or a combination thereof. The conductive material is, for example, a carbon-based material.

[0072] Li 2 S and lithium salts (Li a X1 b ) and metal halides (M a X2 b ) and a conductive material (C) are combined to form Li 2 S-Li a X1 b -M c X2 d -C (1≦a≦5, 1≦b≦5, 1≦c≦5, 1≦d≦5), where X1 is I, Br, Cl, F, H, O, Se, Te, N, P, As, Sb, Al, B, OCl, PF 6 , B.F. 4 , SbF 6 , AsF 6 , ClO 4 , AlO 2 , AlCl 4 , NO 3 , CO 3 , B.H. 4 , S.O. 4 , B.O. 3 , P.O. 4 , NCl, NCl 2 , B.N. 2 or a combination thereof, wherein M is one or more metals selected from Groups 2 to 15 of the Periodic Table, and X2 is I, Br, Cl, F, or a combination thereof. The conductive material is, for example, a carbon-based material.

[0073] Li 2 In S-containing complexes, for example, 1≦a≦4, 1≦b≦4, 1≦c≦4, 1≦d≦4, 1≦a≦3, 1≦b≦3, 1≦c≦3, 1≦d≦3, or 1≦a≦2, 1≦b≦2, 1≦c≦2, 1≦d≦2.

[0074] Li 2The S-containing complex includes a metal halide, and the metal halide can include, for example, one or more metals selected from Al, Mg, Ti, Sn, As, Sb, Nb, Sc, Zr, V, W, Mn, Fe, Co, Pd, Cu, Ag, Zn, and Se. By including such a metal in the metal halide, Li 2 The cycle characteristics of an all-solid-state secondary battery including the S-containing composite can be further improved.

[0075] Li 2 The S-containing complex includes a metal halide, the metal halide being, for example, AlF 3 , AlCl 3 , AlBr 3 ,AlI 3 , MgF 2 , MgCl 2 , MgBr 2 , MgI 2 , TiF 4 , TiCl 4 , TiBr 4 , TiI 4 , SnF 4 , SnCl 4 , SnBr 4 , SnI 4 , AsF 4 , AsCl 4 , AsBr 4 , AsI 4 , SbF 4 , SbCl 4 , SbBr 4 , SbI 4 , or a combination thereof. 2 The S-containing complex contains such metal halides, which allows Li 2 The cycle characteristics of an all-solid-state secondary battery including the S-containing composite can be further improved.

[0076] Li 2 S-containing complexes include, for example, Li 2 A solid solution of S and lithium salt, Li 2 Solid solutions of S and metal halides, Li 2The lithium salt may be a solid solution of S, a lithium salt, a metal halide, or a combination thereof. For example, Li 2 S and lithium salts (Li a X1 b ) and / or Li 2 S and lithium salts (Li a X1 b The composite of Li 2 It can include a solid solution of S and a lithium salt. For example, Li 2 S and metal halides (M c X2 d ) and / or Li 2 S and metal halides (M c X2 d The composite of Li 2 It can contain a solid solution of S and a metal halide. For example, Li 2 S and lithium salts (Li a X1 b ) and metal halides (M a X2 b ) and / or Li 2 S and lithium salts (Li a X1 b ) and metal halides (M a X2 b The composite of Li 2 It may include a solid solution of S, a lithium salt, and a metal halide.

[0077] Li 2 S-containing complexes are Li 2 Solid solution of S and lithium salt, Li 2 Solid solutions of S and metal halides, Li 2 By containing a solid solution of S, a lithium salt, and a metal halide, or a combination thereof, Li 2 The ionic conductivity of S-containing composites can be increased. For example, Li 2 Solid solution of S and lithium salt, Li 2 Solid solutions of S and metal halides, Li 2 A solid solution of S, lithium salt, metal halide, or a combination of these is Li 2S crystallites, containing lithium ions, metal ions and / or halide ions arranged in the crystallites, Li 2 The ionic conductivity of a solid solution of S, lithium salt, and metal halide is Li 2 The ionic conductivity of Li can be improved compared to that of S. 2 The ionic conductivity of the S-containing composite is improved, and the Li 2 The internal resistance of the S-containing composite can be reduced. 2 By including the S-containing composite, the cycle characteristics of the all-solid-state secondary battery including the lithium-containing sulfide-based positive electrode active material can be further improved. For example, the high-rate characteristics of the all-solid-state secondary battery including such a lithium-containing sulfide-based positive electrode active material can be further improved.

[0078] Li 2 S, lithium salt and conductive material composite, Li 2 S, metal halide, conductive material and Li 2 The composite of S, a lithium salt, a metal halide, and a conductive material comprises a conductive material. The conductive material can include, for example, a carbon-based material, a metal-based material, or a combination thereof.

[0079] The carbon-based material can include, for example, a fibrous carbon-based material. The metal-based material can include, for example, a fibrous metal-based material.

[0080] Li 2 The composite of S, metal halide, and conductive material contains a fibrous carbon-based material and / or a fibrous metal-based material, so that Li 2 The electronic conductivity of the composite of S, metal halide, and conductive material can be further improved. 2 The composite of S, metal halide, and conductive material contains a fibrous carbon-based material and / or a fibrous metal-based material, so that Li 2 Electron conduction from the surface to the inside of the composite of S, metal halide, and conductive material can be more easily achieved. 2The internal resistance of the positive electrode active material layer containing the composite of S, a metal halide, and a conductive material is reduced, and the cycle characteristics of the all-solid-state secondary battery containing the positive electrode active material layer can be further improved.

[0081] The aspect ratio of the fibrous carbon-based material and / or the fibrous metal-based material may be, for example, 2 or more, 3 or more, 4 or more, 5 or more, 10 or more, or 20 or more. The aspect ratio of the fibrous carbon-based material and / or the fibrous metal-based material may be, for example, 2 to 30, 3 to 30, 4 to 30, 5 to 30, 10 to 30, or 20 to 30. The aspect ratio of the fibrous carbon-based material and / or the fibrous metal-based material may be, for example, 2 to 30, 2 to 20, 2 to 10, 2 to 8, 2 to 5, or 2 to 4. When the fibrous carbon-based material and / or the fibrous metal-based material has an aspect ratio in such a range, Li 2 The overall electronic conductivity of the composite of S, lithium salt, and conductive material is improved, and Li 2 The imbalance in local electronic conductivity within the composite of S, the lithium salt, and the conductive material is further alleviated.

[0082] The fibrous carbon-based material can include, for example, carbon nanostructures. The carbon nanostructures can include, for example, carbon nanofibers (CNF), carbon nanotubes (CNT), carbon nanobelts, carbon nanorods, or combinations thereof. The fibrous metal-based material can include, for example, metal nanostructures. The metal nanostructures can include, for example, metal nanofibers (MNF), metal nanotubes (MNT), metal nanobelts, metal nanorods, or combinations thereof.

[0083] The carbon nanostructure may include, for example, a primary carbon nanostructure consisting of one carbon nanostructure, a secondary carbon nanostructure formed by aggregating a plurality of primary carbon nanostructures, or a combination thereof.

[0084] The diameter of the primary carbon nanostructure may be, for example, 1 nm to 200 nm, 1 nm to 150 nm, 1 nm to 100 nm, 1 nm to 50 nm, 1 nm to 30 nm, or 1 nm to 20 nm. The length of the primary carbon nanostructure may be, for example, 10 nm to 2 um, 10 nm to 1.5 um, 10 nm to 1 um, 10 nm to 500 nm, 10 nm to 400 nm, 10 nm to 300 nm, 10 nm to 200 nm, or 10 nm to 100 nm. The diameter and length of the primary carbon nanostructure may be measured from a scanning electron microscope (SEM) or a transmission electron microscope (TEM) image. Meanwhile, the diameter and / or length of the primary carbon nanostructure may be measured by a laser diffraction method.

[0085] The secondary carbon nanostructure is, for example, a structure formed by assembling primary carbon nanostructures entirely or partially into a bundle or bundle type. The secondary carbon nanostructure may include, for example, a bundle-type carbon nanostructure, a rope-type carbon nanostructure, or a combination thereof. The diameter of the secondary carbon nanostructure may be, for example, 2 nm to 200 nm, 3 nm to 150 nm, 5 nm to 100 nm, 5 nm to 50 nm, 5 nm to 30 nm, or 5 nm to 20 nm. The length of the secondary carbon nanotube structure may be, for example, 20 nm to 2 μm, 30 nm to 1.5 μm, 50 nm to 1 μm, 50 nm to 500 nm, 50 nm to 400 nm, 50 nm to 300 nm, 50 nm to 200 nm, or 50 nm to 100 nm or more. The diameter and length of the secondary carbon nanostructure may be measured from a scanning electron microscope (SEM) image or an optical microscope. Meanwhile, the diameter and / or length of the secondary carbon nanostructure can be measured by a laser diffraction method. The secondary carbon nanostructure can be, for example, dispersed in a solvent, converted into a primary carbon nanostructure, and then Li 2 It can be used to prepare composites of S, metal halides, and conductive materials.

[0086] The particle size of the sulfide-based positive electrode active material, e.g., Li 2The particle size of the S-containing complex may be, for example, 10 μm or less, 8 μm or less, 5 μm or less, 4 μm or less, 2 μm or less, 1.5 μm or less, or 1 μm or less. 2 The particle size of the S-containing complex may be, for example, 1 to 10 μm, 2 to 10 μm, 2 to 8 μm, or 3 to 8 μm. 2 The particle size of the S-containing complex may be, for example, 0.1 to 10 μm, 0.1 to 8 μm, 0.1 to 5 μm, 0.1 to 4 μm, 0.1 to 2 μm, 0.1 to 1.5 μm, or 0.1 to 1 μm. 2 When the S-containing composite particles have a particle size in such a range, the volume change of the sulfide-based positive electrode active material during charging and discharging is suppressed, and the deterioration of the sulfide-based positive electrode active material during charging and discharging can be more effectively suppressed. 2 If the particle size of the S-containing composite increases excessively, the Li 2 The increased volume change of the S-containing composite may accelerate the degradation of the sulfide-based positive electrode active material. Therefore, the cycle characteristics of the all-solid-state secondary battery containing such a sulfide-based positive electrode active material may be deteriorated. 2 The particle size of the S-containing complex can be measured, for example, using a laser diffraction method, a scanning electron microscope, etc. 2 The size of the S-containing complex is, for example, the arithmetic mean of the particle sizes of multiple particles measured using software in a scanning electron microscope image.

[0087] Li 2 Li in S-containing complexes 2 The particle size may be, for example, 2 μm or less, 1.5 μm or less, or 1 μm or less. 2 The size of the S particles may be, for example, 0.1 to 2 μm, 0.1 to 1.5 μm, or 0.1 to 1 μm or less. 2 The size range of the S particles allows Li 2 The volume change of the S-containing composite is suppressed, and the Li 2 It is possible to suppress the deterioration of the sulfide-based positive electrode active material containing the S-containing composite during charging and discharging. 2If the size of the S particles becomes too large, Li 2 The increase in the volume change of the S-containing complex leads to Li 2 This may accelerate the deterioration of the sulfide-based positive electrode active material containing the S-containing composite, which may result in a decrease in the cycle characteristics of a secondary battery containing such a sulfide-based positive electrode active material.

[0088] Li 2 The ionic conductivity of the S-containing composite is, for example, 1×10 -5 S / cm or more, 2×10 -5 S / cm or more, 4×10 -5 S / cm or more, 6×10 -5 S / cm or more, 8×10 -5 S / cm or 1×10 -4 The ionic conductivity may be 100 S / cm or more. The ionic conductivity can be measured, for example, by using an impedance spectroscopy method, a DC polarization method, or the like. 2 The S-containing composite has an ionic conductivity in such a range, which allows Li 2 The internal resistance of the positive electrode active material layer including the S-containing composite can be further reduced, and the cycle characteristics of the all-solid-state secondary battery including the positive electrode active material layer can be improved.

[0089] Li 2 The electronic conductivity of the S-containing composite is, for example, 1×10 -5 S / cm or more, 2×10 -5 S / cm or more, 4×10 -5 S / cm or more, 6×10 -5 S / cm or more, 8×10 -5 S / cm or 1×10 -4 The electronic conductivity may be 100 S / cm or more. The electronic conductivity can be measured, for example, by using an impedance spectroscopy method, a DC polarization method, or the like. 2The S-containing composite has such a range of electronic conductivity that it is possible to 2 The internal resistance of the positive electrode active material layer containing the S-containing composite can be further reduced. The cycle characteristics of the all-solid-state secondary battery containing the positive electrode active material layer can be improved. 2 For example, Li 2 The composition may include 40 to 80 parts by weight of S, 1 to 40 parts by weight of a combination of a lithium salt and a metal halide, and 1 to 20 parts by weight of a conductive material. The conductive material is, for example, a carbon-based material. In the combination of a lithium salt and a metal halide, the molar ratio of the lithium salt to the metal halide may be, for example, 3:1 to 1:3, 2:1 to 1:2, or 1.5:1 to 1:1.5.

[0090] Li 2 The composite of S, lithium salt, metal halide and conductive material contains Li 2 The S content is, for example, Li 2 For 100 parts by weight of a composite of S, a lithium salt, a metal halide, and a conductive material, Li 2 S may be 10 to 80 parts by weight, 20 to 70 parts by weight, 30 to 60 parts by weight, or 40 to 60 parts by weight. The conductive material is, for example, a carbon-based material.

[0091] Li 2 The content of lithium salt and metal halide contained in the composite of S, lithium salt, metal halide, and conductive material is, for example, Li 2 The combination of the lithium salt and the metal halide may be 10 to 40 parts by weight, 15 to 40 parts by weight, 20 to 40 parts by weight, or 25 to 35 parts by weight, based on 100 parts by weight of the composite of S, the lithium salt, the metal halide, and the conductive material. The conductive material is, for example, a carbon-based material. The molar ratio of the lithium salt to the metal halide may be 3:1 to 1:3.

[0092] Li 2 The conductive material content of the composite of S, a lithium salt, a metal halide, and a conductive material is, for example, Li 2The conductive material may be 1 to 20 parts by weight, 5 to 20 parts by weight, or 5 to 15 parts by weight based on 100 parts by weight of the complex of S, a lithium salt, a metal halide, and a conductive material. The conductive material is, for example, a carbon-based material.

[0093] Li 2 The complex of S, lithium salt, metal halide and conductive material has such a range of Li 2 S, lithium salt, metal halide and conductive material composition, Li 2 A sulfide-based positive electrode active material including a complex of S, a lithium salt, a metal halide, and a conductive material may provide excellent ionic conductivity and / or electronic conductivity.

[0094] Li contained in the positive electrode active material layer 12 2 The S content may be, for example, 30 wt% to 90 wt%, 35 wt% to 90 wt%, 40 wt% to 90 wt%, 45 wt% to 80 wt%, or 50 wt% to 70 wt% of the total weight of the positive electrode active material layer 12.

[0095] The content of the sulfide-based positive electrode active material in the positive electrode active material layer 12 may be, for example, 10 wt% to 90 wt%, 10 wt% to 80 wt%, 10 wt% to 70 wt%, 10 wt% to 60 wt%, or 10 wt% to 50 wt% of the total weight of the positive electrode active material layer 12. On the other hand, the content of the sulfide-based positive electrode active material in the positive electrode active material layer 12 may be, for example, 10 wt% to 90 wt%, 20 wt% to 90 wt%, 30 wt% to 90 wt%, 30 wt% to 90 wt%, or 30 wt% to 90 wt% of the total weight of the positive electrode active material layer 12.

[0096] The positive electrode active material layer 12 is, for example, Li 2 The sulfide-based compound may further include a sulfide-based compound classified as Li and S. The sulfide-based compound may be, for example, a compound containing a metal element other than Li and a sulfur element. The sulfide-based compound may be, for example, a compound containing a metal element belonging to Groups 1 to 14 of the periodic table with an atomic weight of 10 or more and a sulfur element. The sulfide-based compound may be, for example, FeS 2 , V.S. 2, NaS, MnS, FeS, NiS, CuS, or a combination thereof. When the positive electrode active material layer further contains a sulfide-based compound, the cycle characteristics of the all-solid-state secondary battery can be further improved. 2 The content of the sulfide-based compound classified as S may be 10 wt % or less, 5 wt % or less, 3 wt % or less, or 1 wt % or less of the total weight of the positive electrode active material layer 12 .

[0097] [Positive electrode layer: solid electrolyte] The positive electrode active material layer 12 may further include, for example, a solid electrolyte. The solid electrolyte may be, for example, a sulfide-based solid electrolyte. The solid electrolyte included in the positive electrode layer 10 may be the same as or different from the solid electrolyte included in the solid electrolyte layer 30. For details about the solid electrolyte, see the section on the solid electrolyte layer 30.

[0098] The solid electrolyte contained in the positive electrode active material layer 12 has a smaller D50 average particle diameter than the solid electrolyte contained in the solid electrolyte layer 30. For example, the D50 average particle diameter of the solid electrolyte contained in the positive electrode active material layer 12 is 90% or less, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, or even 20% or less of the D50 average particle diameter of the solid electrolyte contained in the solid electrolyte layer 30. The D50 average particle diameter is, for example, a median particle diameter (D50). The median particle diameter (D50) is, for example, a particle size corresponding to a 50% cumulative volume calculated from the particle side having a small particle size in a particle size distribution measured by a laser diffraction method.

[0099] The solid electrolyte content in the positive electrode active material layer 12 may be, for example, 1 wt % to 40 wt %, 1 wt % to 30 wt %, 1 wt % to 20 wt %, or 1 wt % to 10 wt % of the total weight of the positive electrode active material layer 12.

[0100] [Positive electrode layer: conductive material] The positive electrode active material layer 12 may further include a conductive material. The conductive material may be, for example, a carbon-based conductive material, a metal-based conductive material, or a combination thereof. The carbon-based conductive material may be, for example, graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or a combination thereof, but is not limited thereto, and any material used as a carbon-based conductive material in the relevant technical field may be used. The metal-based conductive material may be, for example, metal powder, metal fiber, or a combination thereof, but is not limited thereto, and any material used as a metal-based conductive material in the relevant technical field may be used. The conductive material content of the positive electrode active material layer 12 may be, for example, 1 wt% to 30 wt%, 1 wt% to 20 wt%, or 1 wt% to 10 wt% of the total weight of the positive electrode active material layer 12.

[0101] [Positive electrode layer: binder] The positive electrode active material layer 12 may further include a binder. The binder is, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited thereto, and any binder used as a binder in the relevant technical field can be used. The content of the binder contained in the positive electrode active material layer 12 may be, for example, 1 wt % to 10 wt % of the total weight of the positive electrode active material layer 12. The binder can be omitted.

[0102] [Positive electrode layer: Other additives] The positive electrode active material layer 12 may further contain additives such as a filler, a coating agent, a dispersant, and an ion-conductive auxiliary in addition to the above-mentioned positive electrode active material, solid electrolyte, binder, and conductive material.

[0103] As the filler, coating agent, dispersant, ion-conductive auxiliary agent, and the like contained in the positive electrode active material layer 12, known materials generally used for electrodes of all-solid-state secondary batteries can be used.

[0104] [Positive electrode layer: positive electrode current collector] The positive electrode current collector 11 is, for example, a plate or foil made of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The positive electrode current collector 11 can be omitted. The thickness of the positive electrode current collector 11 is, for example, 1 μm to 100 μm, 1 μm to 50 μm, 5 μm to 25 μm, or 10 μm to 20 μm.

[0105] The positive electrode current collector 11 includes, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The base film may be, for example, an insulator. When the base film includes an insulating thermoplastic polymer, the base film is softened or liquefied in the event of a short circuit, thereby cutting off the operation of the battery and suppressing a sudden increase in current. The metal layer may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), or an alloy thereof. The metal layer acts as an electrochemical fuse and is cut off in the event of an overcurrent, thereby preventing a short circuit. The limit current and maximum current can be adjusted by adjusting the thickness of the metal layer. The metal layer is plated or deposited on the base film. If the thickness of the metal layer is reduced, the limit current and / or maximum current of the positive electrode current collector 11 decreases, thereby improving the stability of the lithium battery in the event of a short circuit. A lead tab can be added on the metal layer for connection to the outside. The lead tab is welded to the metal layer or the metal layer / base film laminate by ultrasonic welding, laser welding, spot welding, etc. During welding, the base film and / or metal layer melts and the metal layer is electrically connected to the lead tab. A metal chip can be added between the metal layer and the lead tab to make the welding between the metal layer and the lead tab stronger. The metal chip can be a thin piece of the same material as the metal of the metal layer. The metal piece may be, for example, a metal foil, a metal mesh, or the like.The metal piece may be, for example, aluminum foil, copper foil, SUS foil, etc. The lead tab is welded to the metal piece / metal layer laminate or the metal piece / metal layer / base film laminate by disposing the metal piece on the metal layer and then welding it to the lead tab. During welding, the base film, the metal layer, and / or the metal piece melts, and the metal layer or the metal layer / metal piece laminate is electrically connected to the lead tab. The metal piece and / or the lead tab may be added to a portion on the metal layer. The thickness of the base film may be, for example, 1 to 50 μm, 1.5 to 50 μm, 1.5 to 40 μm, or 1 to 30 μm. The weight of the electrode assembly can be more effectively reduced by the base film having a thickness in such a range. The melting point of the base film may be, for example, 100 to 300° C., 100 to 250° C., or 100 to 200° C. Since the base film has a melting point in such a range, the base film is melted in the process of welding the lead tab, and can be easily bonded to the lead tab. In order to improve the adhesive strength between the base film and the metal layer, a surface treatment such as a corona treatment can be performed on the base film. The thickness of the metal layer may be, for example, 0.01 to 3 μm, 0.1 to 3 μm, 0.1 to 2 μm, or 0.1 to μm. Since the metal layer has a thickness in such a range, the stability of the electrode assembly can be ensured while maintaining the conductivity. The thickness of the metal piece may be, for example, 2 to 10 μm, 2 to 7 μm, or 4 to 6 μm. Since the metal piece has a thickness in such a range, the connection between the metal layer and the lead tab can be more easily performed. Since the positive electrode current collector 11 has such a structure, the weight of the positive electrode can be reduced, and as a result, the energy density of the positive electrode and the lithium battery can be improved.

[0106] [Positive electrode layer: first inactive material] 1, the positive electrode layer 10 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on one side of the positive electrode current collector. A first inactive member 40 is disposed on one side of the positive electrode layer 10. The first inactive member 40 is disposed on one side of the positive electrode active material layer 12 and the positive electrode current collector 11. Referring to FIG. 2, the first inactive member 40 is disposed on one side of the positive electrode active material layer 12, and is disposed between the solid electrolyte layer 30 and the positive electrode current collector 11 facing the solid electrolyte layer 30. The first inactive member 40 is not disposed on one side of the positive electrode current collector 11.

[0107] The inclusion of the first inactive member 40 prevents cracks in the solid electrolyte layer 30 during manufacture of the all-solid-state secondary battery 1 and / or during charging and discharging, resulting in improved cycle characteristics of the all-solid-state secondary battery 1. In an all-solid-state secondary battery 1 that does not include the first inactive member 40, cracks are generated in the solid electrolyte layer 30 due to uneven pressure being applied to the solid electrolyte layer 30 that contacts the positive electrode layer 10 during manufacture of the all-solid-state secondary battery 1 and / or during charging and discharging, increasing the possibility of short circuiting due to the growth of lithium metal through the cracks.

[0108] In the all-solid-state secondary battery 1, the thickness T2 of the first inactive member 40 is thinner than or equal to the thickness T1 of the positive electrode active material layer 12. In the all-solid-state secondary battery 1, the thickness T2 of the first inactive member 40 is substantially equal to the thickness T3 of the positive electrode layer 10. Since the thickness T2 of the first inactive member 40 is equal to the thickness T3 of the positive electrode layer 10, a uniform pressure is applied between the positive electrode layer 10 and the solid electrolyte layer 30, and the positive electrode layer 10 and the solid electrolyte layer 30 are sufficiently adhered to each other, thereby reducing the interface resistance between the positive electrode layer 10 and the solid electrolyte layer 30. In addition, the solid electrolyte layer 30 is sufficiently sintered during the pressurized manufacturing process of the all-solid-state secondary battery 1, thereby reducing the internal resistance of the solid electrolyte layer 30 and the all-solid-state secondary battery 1 including it.

[0109] The first inactive member 40 surrounds the side of the positive electrode layer 10 and contacts the solid electrolyte layer 30. The first inactive member 40 surrounds the side of the positive electrode layer 10 and contacts the solid electrolyte layer 30, so that cracks in the solid electrolyte layer 30 that are not in contact with the positive electrode layer 10 due to a pressure difference during a pressing process can be effectively suppressed. The first inactive member 40 surrounds the side of the positive electrode layer 10 and is separated from the negative electrode layer 20, more specifically, the first negative electrode active material layer 22. The first inactive member 40 surrounds the side of the positive electrode layer 10 and contacts the solid electrolyte layer 30, and is separated from the negative electrode layer 20. Therefore, the physical contact between the positive electrode layer 10 and the first negative electrode active material layer 22 suppresses the occurrence of a short circuit or the occurrence of a short circuit due to overcharging of lithium. For example, by arranging the inactive member 40 on one side of the positive electrode active material layer 12 and also on one side of the positive electrode current collector 11, the possibility of a short circuit occurring due to contact between the positive electrode current collector 11 and the negative electrode layer 20 is more effectively suppressed.

[0110] 1 to 5, the first inactive members 40, 40a, and 40b extend from one side of the positive electrode layer 10 to an end of the solid electrolyte layer 30. The first inactive member 40 extends to the end of the solid electrolyte layer 30, thereby suppressing the occurrence of cracks at the end of the solid electrolyte layer 30. The end of the solid electrolyte layer 30 is the outermost part that contacts the side of the solid electrolyte layer 30. The first inactive member 40 extends to the outermost part that contacts the side of the solid electrolyte layer 30. The first inactive member 40 is separated from the negative electrode layer 20, more specifically, the first negative electrode active material layer 22. The first inactive member 40 extends to the end of the solid electrolyte layer 30 but does not contact the negative electrode layer 20. The first inactive member 40 fills a space that extends to the end of the solid electrolyte layer 30 on one side of the positive electrode layer 10, for example.

[0111] 1 and 2, the width W2 of the first inactive member 40 extending from one side of the positive electrode layer 10 to the end of the solid electrolyte layer 30 is, for example, 1 to 30%, 1 to 25%, 1 to 20%, 1 to 15%, 1 to 10%, or 1 to 5% of the width W1 between one side of the positive electrode layer 10 and the other side opposite the one side. Referring to FIG. 1 and FIG. 2, the width W2 of the first inactive member 40 extending from one side of the positive electrode layer 10 to the end of the solid electrolyte layer 30 is, for example, 1 to 30%, 3 to 30%, 5 to 30%, 5 to 20%, 5 to 15%, or 5 to 10% of the width W1 between one side of the positive electrode layer 10 and the other side opposite the one side. If the width W2 of the first inactive member 40 is excessively large, the energy density of the all-solid-state secondary battery 1 is reduced. If the width W2 of the first inactive member 40 is too small, the effect of disposing the first inactive member 40 is negligible.

[0112] Area S1 of the positive electrode layer 10 For example, the area S1 of the positive electrode active material layer 12 (for example, the cross-sectional area S1 of the positive electrode layer 10 in the stacking direction or thickness direction of the all-solid-state secondary battery 1, or the cross-sectional area S1 of the positive electrode active material layer 12) is smaller than the area S3 of the solid electrolyte layer 30 in contact with the positive electrode layer 10 (or the positive electrode active material layer 12) (for example, the cross-sectional area S3 of the solid electrolyte layer 30 in the stacking direction or thickness direction of the all-solid-state secondary battery 1). The flame-retardant inactive member 40 surrounds the side surface of the positive electrode layer 10 (or the positive electrode active material layer 12) and compensates for the area difference between the positive electrode layer 10 and the solid electrolyte layer 30. The area S2 of the flame-retardant inactive member 40 compensates for the difference between the area S1 of the positive electrode layer 10 (or the positive electrode active material layer 12) and the area S3 of the solid electrolyte layer 30, thereby effectively suppressing cracks in the solid electrolyte layer 30 caused by the pressure difference during the pressing process. For example, the sum of the area S1 of the positive electrode layer 10 and the area S2 of the inactive member 40 is equal to the area S3 of the solid electrolyte layer 30.

[0113] The area S1 of the positive electrode layer 10 (or the positive electrode active material layer 12) is, for example, less than 100%, 99% or less, 98% or less, 97% or less, 96% or less, or 95% or less of the area S3 of the solid electrolyte layer 30. The area S1 of the positive electrode layer 10 (or the positive electrode active material layer 12) is, for example, 50% to less than 100%, 50% to 99%, 55% to 98%, 60% to 97%, 70% to 96%, 80% to 95%, or 85% to 95% of the area S3 of the solid electrolyte layer 30.

[0114] If the area S1 of the positive electrode layer 10 (or the positive electrode active material layer 12) is equal to or greater than the area S3 of the solid electrolyte layer 30, a short circuit may occur due to physical contact between the positive electrode layer 10 and the first negative electrode active material layer 22, or the possibility of a short circuit occurring due to overcharging of lithium or the like increases. The area S1 of the positive electrode layer 10 (or the positive electrode active material layer 12) is, for example, equal to the area of ​​the positive electrode active material layer 12. The area S1 of the positive electrode layer 10 is, for example, equal to the area of ​​the positive electrode current collector 11.

[0115] The area S2 of the first inactive member 40 is, for example, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the area S1 of the positive electrode layer 10 (or the positive electrode active material layer 12). The area S2 of the first inactive member 40 is, for example, 1% to 50%, 5% to 40%, 5% to 30%, 5% to 20%, or 5% to 15% of the area S1 of the positive electrode layer 10.

[0116] The area S1 of the positive electrode layer 10 (or the positive electrode active material layer 12) is smaller than the area S4 of the negative electrode current collector 21 (for example, the cross-sectional area S4 of the negative electrode current collector 21 in the stacking direction or thickness direction of the all-solid-state secondary battery 1). The area S1 of the positive electrode layer 10 (or the positive electrode active material layer 12) is, for example, less than 100%, 99% or less, 98% or less, 97% or less, 96% or less, or 95% or less of the area S4 of the negative electrode current collector 21. The area S1 of the positive electrode layer 10 (or the positive electrode active material layer 12) is, for example, 50% to less than 100%, 50% to 99%, 55% to 98%, 60% to 97%, 70% to 96%, 80% to 95%, or 85% to 95% of the area S4 of the negative electrode current collector 21. The area S4 of the negative electrode current collector 21 is, for example, the same as the area of ​​the negative electrode layer 20 (for example, the cross-sectional area of ​​the negative electrode layer 20 in the stacking direction or thickness direction of the all-solid-state secondary battery 1). The area S4 of the negative electrode current collector 21 is, for example, the same as the area of ​​the first negative electrode active material layer 22 (for example, the cross-sectional area of ​​the first negative electrode active material layer 22 in the stacking direction or thickness direction of the all-solid-state secondary battery 1).

[0117] As used herein, the term "same" area, length, width, thickness and / or shape includes all cases of having "substantially the same" area, length, width, thickness and / or shape, except when the area, length, width, thickness and / or shape are intentionally different from each other. The term "same" area, length, width and / or thickness includes a range in which the unintentional difference between the areas, lengths, widths and / or thicknesses of the objects being compared is, for example, less than 1%, less than 0.5%, or less than 0.1%.

[0118] The thickness of the first inactive member 40 is, for example, greater than the thickness of the first negative electrode active material layer 22. The thickness of the first negative electrode active material layer 22 is, for example, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the thickness of the first inactive member 40. The thickness of the first negative electrode active material layer 22 is, for example, 1% to 50%, 1% to 40%, 1% to 30%, 1% to 20%, or 1% to 10% of the thickness of the first inactive member 40.

[0119] The negative electrode layer 20 includes a negative electrode current collector 21 and a first negative electrode active material layer 22 disposed on one surface of the negative electrode current collector 21. For example, the first negative electrode active material layer 22 is free on the other surface opposite to the one surface of the negative electrode current collector 21. For example, the first negative electrode active material layer 22 is disposed only on one surface of the negative electrode current collector 21, and the first negative electrode active material layer 22 is not disposed on the other surface.

[0120] The first inactive member 40 may be a gasket. By using a gasket as the inactive member 40, cracks in the solid electrolyte layer 30 caused by a pressure difference during a pressing process can be effectively suppressed.

[0121] The first inactive member 40 has, for example, a single-layer structure. Alternatively, although not shown, the first inactive member 40 may have a multi-layer structure. In the first inactive member 40 having a multi-layer structure, each layer has a different composition. The first inactive member having a multi-layer structure has, for example, a two-layer structure, a three-layer structure, a four-layer structure, or a five-layer structure. The first inactive member 40 having a multi-layer structure may include, for example, one or more adhesive layers and one or more support layers. The adhesive layer effectively prevents separation between the positive electrode layer 10 and the solid electrolyte layer 30 due to a volume change of the positive electrode layer 10 that occurs during the charging and discharging process of the all-solid-state secondary battery 1, and provides a binding force between the support layer and other layers, thereby improving the film strength of the first inactive member 40. The support layer provides a supporting force to the first inactive member 40, prevents non-uniformity in the pressure applied to the solid electrolyte layer 30 during the pressurizing process or the charging and discharging process, and prevents deformation of the manufactured all-solid-state secondary battery 1.

[0122] 3, the all-solid-state secondary battery 1 includes a positive electrode layer 10, a negative electrode layers 20, 20a, 20b, and solid electrolyte layers 30, 30a, 30b disposed therebetween. The positive electrode layer 10 includes a positive electrode current collector 11 and a first positive electrode active material layer 12a and a second positive electrode active material layer 12b disposed on both sides of the positive electrode current collector 11, respectively. The solid electrolyte layer 30 includes a first solid electrolyte layer 30a in contact with the first positive electrode active material layer 12a and a second solid electrolyte layer 30b in contact with the second positive electrode active material layer 12b, respectively. The negative electrode layer 20 includes a first negative electrode layer 20a in contact with the first solid electrolyte layer 30a and a second negative electrode layer 20b in contact with the second solid electrolyte layer 30b, respectively. A first inactive member 40 is disposed between the first solid electrolyte layer 30a and the second solid electrolyte layer 30b facing each other to surround the side surface of the positive electrode layer 10. The first inactive member 40 includes, for example, a 1a inactive member 40a in contact with the first solid electrolyte layer 30a, and a 1b inactive member 40b in contact with the second solid electrolyte layer 30b. Therefore, the all-solid-state secondary battery 1 has a bi-cell structure. Since the all-solid-state secondary battery 1 has such a bi-cell structure, the solid electrolyte layer 30 and the negative electrode layer 20 are arranged symmetrically facing each other with the positive electrode layer 10 at the center, and structural deformation due to pressure applied during the manufacture of the all-solid-state secondary battery 1 is more efficiently suppressed. Therefore, cracks in the solid electrolyte layer 30 during the manufacturing process and / or charge / discharge process of the all-solid-state secondary battery 1 are suppressed, and short-circuiting of the all-solid-state secondary battery 1 due to the cracks is prevented, and as a result, the cycle characteristics of the all-solid-state secondary battery 1 are further improved. In addition, since only one positive electrode current collector 11 is used for the multiple positive electrode active material layers 12a and 12b, the energy density of the all-solid-state secondary battery 1 is increased.

[0123] 1 to 5, the first inactive member 40 is, for example, a flame-retardant inactive member. The flame-retardant inactive member provides flame retardancy, thereby preventing the possibility of thermal runaway and ignition of the all-solid-state secondary battery 1. As a result, the safety of the all-solid-state secondary battery 1 is further improved. The flame-retardant inactive member absorbs residual moisture in the all-solid-state secondary battery 1, thereby preventing deterioration of the all-solid-state secondary battery 1 and improving the life characteristics of the all-solid-state secondary battery 1.

[0124] The flame-retardant inert member includes, for example, a matrix and a filler. The matrix includes, for example, a substrate and a reinforcing material. The matrix includes, for example, a fibrous substrate and a fibrous reinforcing material. When the matrix includes the substrate, it can have elasticity. Therefore, the matrix can effectively accommodate the volume change during charging and discharging of the all-solid-state secondary battery 1 and can be arranged at various positions. The substrate included in the matrix includes, for example, a first fibrous material. When the substrate includes the first fibrous material, it can effectively accommodate the volume change of the positive electrode layer 10 that occurs during the charging and discharging process of the all-solid-state secondary battery 1 and can effectively suppress the deformation of the first inert member 40 due to the volume change of the positive electrode layer 10. The first fibrous material is, for example, a material having an aspect ratio of 5 or more, 20 or more, or 50 or more. The first fibrous material is, for example, a material having an aspect ratio of 5 to 1000, 20 to 1000, or 50 to 1000. The first fibrous material is, for example, an insulating material. The first fibrous material is an insulating material, and therefore can effectively prevent a short circuit between the positive electrode layer 10 and the negative electrode layer 20 caused by lithium dendrites or the like that occur during the charging and discharging process of the all-solid-state secondary battery 1. The first fibrous material includes, for example, one or more selected from pulp fibers, insulating polymer fibers, and ion-conductive polymer fibers. The matrix includes a reinforcing material, which improves the strength of the matrix. Therefore, the matrix can prevent an excessive volume change during charging and discharging of the all-solid-state secondary battery 1, and can prevent deformation of the all-solid-state secondary battery. The reinforcing material included in the matrix includes, for example, a second fibrous material. The reinforcing material includes the second fibrous material, which can further uniformly increase the strength of the matrix. The second fibrous material is, for example, a material having an aspect ratio of 3 or more, 5 or more, or 10 or more. The first fibrous material is, for example, a material having an aspect ratio of 3 to 100, 5 to 100, or 10 to 100. The second fibrous material is, for example, a flame-retardant material. The second fibrous material is a flame-retardant material, which can effectively prevent ignition due to thermal runaway that occurs during the charge / discharge process or due to external impact of the all-solid-state secondary battery 1. Examples of the second fibrous material include glass fiber, metal oxide fiber, and ceramic fiber.

[0125] The flame-retardant inert member includes a filler in addition to the matrix. The filler may be disposed inside the matrix, on the surface of the matrix, or on both the inside and the surface. The filler is, for example, an inorganic material. The filler included in the flame-retardant inert member is, for example, a moisture getter. The filler removes moisture remaining in the all-solid-state secondary battery 1 by adsorbing moisture at a temperature of, for example, less than 100°C, thereby preventing deterioration of the all-solid-state secondary battery 1. In addition, if the temperature of the all-solid-state secondary battery 1 increases to 150°C or higher due to thermal runaway generated during the charge / discharge process of the all-solid-state secondary battery 1 or due to external impact, the filler can release the adsorbed moisture to effectively suppress ignition of the all-solid-state secondary battery 1. That is, the filler is, for example, a flame retardant. The filler is, for example, a metal hydroxide having moisture adsorption properties. The metal hydroxide included in the filler is, for example, Mg(OH) 2 , Fe(OH) 3 , Sb(OH) 3 , Sn(OH) 4 , TI(OH) 3 , Zr(OH) 4 , Al(OH) 3 The content of the filler in the flame-retardant inert member is, for example, 10 to 80 parts by weight, 20 to 80 parts by weight, 30 to 80 parts by weight, 40 to 80 parts by weight, 50 to 80 parts by weight, 60 to 80 parts by weight, or 65 to 80 parts by weight, relative to 100 parts by weight of the flame-retardant inert member 40.

[0126] The flame-retardant inert member 40 may further include, for example, a binder. The binder may include, for example, a curable polymer or a non-curable polymer. The curable polymer is a polymer that is cured by heat and / or pressure. The curable polymer is, for example, a solid at room temperature. The flame-retardant inert member 40 includes, for example, a heat-pressure curable film and / or a cured product thereof. The heat-pressure curable polymer is, for example, TSA-66 by Toray.

[0127] The flame-retardant inert member may further include other materials in addition to the above-mentioned substrate, reinforcing material, filler, and binder. The flame-retardant inert member may further include one or more selected from, for example, paper, insulating polymer, ion-conducting polymer, insulating inorganic material, oxide-based solid electrolyte, and sulfide-based solid electrolyte. The insulating polymer may be, for example, an olefin-based polymer such as polypropylene (PP) or polyethylene (PE).

[0128] The density of the base material or the density of the reinforcing material contained in the flame-retardant inactive member may be, for example, 10% to 300%, 10% to 150%, 10% to 140%, 10% to 130%, or 10% to 120% of the density of the positive electrode active material contained in the positive electrode active material layer 12.

[0129] The first inactive member 40 is a member that does not contain a material having electrochemical activity, for example, an electrode active material. The electrode active material is a material that absorbs / desorbs lithium. The first inactive member 40 is a member made of a material other than the electrode active material that is used in the technical field.

[0130] [Negative electrode layer] [Negative electrode layer: negative electrode active material] 1 to 5, the negative electrode layer 20 includes a first negative electrode active material layer 22. The first negative electrode active material layer 22 includes, for example, a negative electrode active material and a binder. The negative electrode active material included in the first negative electrode active material layer 22 is, for example, a negative electrode material capable of forming an alloy or a compound with lithium.

[0131] The negative electrode active material contained in the first negative electrode active material layer 22 has, for example, a particulate shape. The average particle diameter of the particulate negative electrode active material is, for example, 4 μm or less, 3 μm or less, 2 μm or less, 1 μm or less, 500 nm or less, 300 nm or less, or 100 nm or less. The average particle diameter of the particulate negative electrode active material is, for example, 10 nm to 4 μm, 10 nm to 3 μm, 10 nm to 2 μm, 10 nm to 1 μm, 10 nm to 500 nm, 10 nm to 300 nm, or 10 nm to 100 nm. When the negative electrode active material has an average particle diameter in such a range, reversible absorbing and / or desorbing of lithium during charging and discharging is further facilitated. The average particle diameter of the negative electrode active material is, for example, a median diameter (D50) measured using a laser type particle size distribution meter.

[0132] The negative electrode active material contained in the first negative electrode active material layer 22 includes, for example, one or more selected from a carbon-based negative electrode active material and a metal or semi-metal negative electrode active material.

[0133] Carbon-based negative electrode active materials include, for example, amorphous carbon, crystalline carbon, porous carbon, or a combination thereof.

[0134] The carbon-based negative electrode active material is, in particular, amorphous carbon. Examples of amorphous carbon include, but are not limited to, carbon black (CB), acetylene black (AB), furnace black (FB), ketjen black (KB), graphene, etc., and any material that is classified as amorphous carbon in the art can be used. Amorphous carbon is carbon that has no crystallinity or has very low crystallinity, and is classified as crystalline carbon or graphite-based carbon.

[0135] The carbon-based negative electrode active material may be, for example, porous carbon. The pore volume of the porous carbon is, for example, 0.1 cc / g to 10.0 cc / g, 0.5 cc / g to 5 cc / g, or 0.1 cc / g to 1 cc / g. The average pore diameter of the porous carbon is, for example, 1 nm to 50 nm, 1 nm to 30 nm, or 1 nm to 10 nm. The BET specific surface area of ​​the porous carbon is, for example, 100 m 2 / g~3000m 2 The BET specific surface area of ​​the porous carbon can be measured, for example, according to ISO 9277:2022.

[0136] The metal or semi-metal negative electrode active material includes, but is not necessarily limited to, one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn), and any metal or semi-metal negative electrode active material that forms an alloy or compound with lithium in the art can be used. For example, nickel (Ni) does not form an alloy with lithium, so nickel (Ni) is not a metal negative electrode active material.

[0137] The first negative electrode active material layer 22 includes one of the negative electrode active materials or a mixture of a plurality of different negative electrode active materials. For example, the first negative electrode active material layer 22 includes only amorphous carbon, or includes one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). Differently, the first negative electrode active material layer 22 includes a mixture of amorphous carbon and one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). The mixing ratio of the mixture of amorphous carbon and gold, etc., by weight is, for example, 99:1 to 1:99, 10:1 to 1:2, 5:1 to 1:1, or 4:1 to 2:1, but is not necessarily limited to such ranges and is selected depending on the required characteristics of the all-solid-state secondary battery 1. When the negative electrode active material has such a composition, the cycle characteristics of the all-solid-state secondary battery 1 are further improved.

[0138] The negative electrode active material contained in the first negative electrode active material layer 22 includes, for example, a mixture of first particles made of amorphous carbon and second particles made of a metal or a metalloid. The metal or metalloid includes, for example, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). Alternatively, the metalloid is a semiconductor. The content of the second particles is 1 to 99 wt%, 1 to 60 wt%, 8 to 60 wt%, 10 to 50 wt%, 15 to 40 wt%, or 20 to 30 wt%, based on the total weight of the mixture. When the second particles have a content in such a range, for example, the cycle characteristics of the all-solid-state secondary battery 1 are further improved.

[0139] Alternatively, the first negative electrode active material layer 22 includes a composite negative electrode active material. The composite negative electrode active material includes, for example, a carbon-based support and a metal-based negative electrode active material supported on the carbon-based support. When the composite negative electrode active material has such a structure, uneven distribution of the metal-based negative electrode active material is prevented in the first negative electrode active material layer, and a uniform distribution is obtained. As a result, the cycle characteristics of the all-solid-state secondary battery 1 including the first negative electrode active material layer 22 are further improved.

[0140] The metal-based negative electrode active material supported on the carbon-based support includes, for example, a metal, a metal oxide, a composite of a metal and a metal oxide, or a combination thereof. The metal includes, for example, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), tellurium (Te), and zinc (Zn). The metal oxide includes, for example, gold (Au) oxide, platinum (Pt) oxide, palladium (Pd) oxide, silicon (Si) oxide, silver (Ag) oxide, aluminum (Al) oxide, bismuth (Bi) oxide, tin (Sn) oxide, tellurium (Te) oxide, and zinc (Zn) oxide. The metal oxide includes, for example, AuxOy (0 < x ≤ 2, 0 < y ≤ 3), PtxOy (0 < x ≤ 1, 0 < y ≤ 2), PdxOy (0 < x ≤ 1, 0 < y ≤ 1), SixOy (0 < x ≤ 1, 0 < y ≤ 2), AgxOy (0 < x ≤ 2, 0 < y ≤ 1), AlxOy (0 < x ≤ 2, 0 < y ≤ 3), BixOy (0 < x ≤ 2, 0 < y ≤ 3), SnxOy (0 < x ≤ 1, 0 < y ≤ 2), TexOy (0 < x ≤ 1, 0 < y ≤ 3), ZnxOy (0 < x ≤ 1, 0 < y ≤ 1), or a combination thereof. The composite of a metal and a metal oxide includes, for example, a composite of Au and AuxOy (0 < x ≤ 2, 0 < y ≤ 3), a composite of Pt and PtxOy (0 < x ≤ 1, 0 < y ≤ 2), a composite of Pd and PdxOy (0 < x ≤ 1, 0 < y ≤ 1), a composite of Si and SixOy (0 < x ≤ 1, 0 < y ≤ 2), a composite of Ag and AgxOy (0 < x ≤ 2, 0 < y ≤ 1), a composite of Al and AlxOy (0 < x ≤ 2, 0 < y ≤ 3), a composite of Bi and BixOy (0 < x ≤ 2, 0 < y ≤ 3), a composite of Sn and SnxOy (0 < x ≤ 1, 0 < y ≤ 2), a composite of Te and TexOy (0 < x ≤ 1, 0 < y ≤ 3), a composite of Zn and ZnxOy (0 < x ≤ 1, 0 < y ≤ 1), or a combination thereof.

[0141] The carbon-based support is, for example, amorphous carbon. Examples of amorphous carbon include, but are not limited to, carbon black (CB), acetylene black (AB), furnace black (FB), ketjen black (KB), graphene, activated carbon, carbon nanofiber (CNF), and carbon nanotube (CNT). Any material that is classified as amorphous carbon in the art can be used. Amorphous carbon is carbon that has no crystallinity or has very low crystallinity, and is classified as crystalline carbon or graphite-based carbon. The carbonaceous material is, for example, a carbon-based negative electrode active material.

[0142] The composite negative electrode active material may, for example, be particulate. The particle size of the particulate composite negative electrode active material may, for example, be 10 nm to 4 μm, 10 nm to 1 μm, 10 nm to 500 nm, 10 nm to 200 nm, or 10 nm to 100 nm. When the composite negative electrode active material has a particle size in such a range, reversible absorption and / or desorbing of lithium during charging and discharging is further facilitated. The metal-based negative electrode active material supported on the support may, for example, be particulate. The particle size of the metal-based negative electrode active material may, for example, be 1 nm to 200 nm, 1 nm to 150 nm, 5 nm to 100 nm, or 10 nm to 50 nm. The carbon-based support may, for example, be particulate. The particle size of the carbon-based support may be, for example, 10 nm to 2 μm, 10 nm to 1 μm, 10 nm to 500 nm, 10 nm to 200 nm, or 10 nm to 100 nm. By having the carbon-based support have a particle size in such a range, it can be more uniformly arranged in the first negative electrode active material layer. The carbon-based support may be, for example, nanoparticles having a particle size of 500 nm or less. The particle size of the composite negative electrode active material, the particle size of the metal-based negative electrode active material, and the particle size of the carbon-based support are, for example, average particle sizes. The average particle size is, for example, a median diameter (D50) measured using a laser type particle size distribution meter. Alternatively, the average particle size may be, for example, automatically determined using software from an electron microscope image, or may be passively determined manually.

[0143] [Negative electrode layer: binder] The binder contained in the first negative electrode active material layer 22 is, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but is not necessarily limited thereto, and any binder used as a binder in the relevant technical field can be used. The binder can be composed of a single binder or a plurality of different binders.

[0144] Since the first negative electrode active material layer 22 contains a binder, the first negative electrode active material layer 22 is stabilized on the negative electrode current collector 21. In addition, cracks in the first negative electrode active material layer 22 are suppressed despite volume changes and / or relative position changes of the first negative electrode active material layer 22 during charge and discharge. For example, when the first negative electrode active material layer 22 does not contain a binder, the first negative electrode active material layer 22 can be easily separated from the negative electrode current collector 21. When the first negative electrode active material layer 22 is detached from the negative electrode current collector 21, the negative electrode current collector 21 comes into contact with the solid electrolyte layer 30 at the exposed portion of the negative electrode current collector 21, increasing the possibility of short circuit occurrence. The first negative electrode active material layer 22 is prepared, for example, by applying a slurry in which materials constituting the first negative electrode active material layer 22 are dispersed onto the negative electrode current collector 21 and drying the slurry. The negative electrode active material can be stably dispersed in the slurry by including a binder in the first negative electrode active material layer 22. For example, when the slurry is applied onto the negative electrode current collector 21 by a screen printing method, clogging of the screen (for example, clogging due to aggregates of the negative electrode active material) can be suppressed.

[0145] [Negative electrode layer: Other additives] The first negative electrode active material layer 22 may further include additives used in the conventional all-solid-state secondary battery 1, such as a filler, a coating agent, a dispersant, an ion-conductive auxiliary, and the like.

[0146] [Negative electrode layer: solid electrolyte] The first negative electrode active material layer 22 may further include a solid electrolyte. The solid electrolyte may be, for example, a material selected from the solid electrolytes included in the solid electrolyte layer 30. The solid electrolyte included in the first negative electrode active material layer 22 acts as a reaction site where lithium metal begins to be formed in the first negative electrode active material layer 22, acts as a space in which the formed lithium metal is stored, or acts as a path for transporting lithium ions. The solid electrolyte is optional.

[0147] In the first negative electrode active material layer 22, the content of the solid electrolyte is, for example, high in a region adjacent to the solid electrolyte layer 30 and low in a region adjacent to the negative electrode current collector 21. In the first negative electrode active material layer 22, the solid electrolyte may have a concentration gradient in which the concentration decreases from the region adjacent to the solid electrolyte layer 30 to the region adjacent to the negative electrode current collector 21.

[0148] [Negative electrode layer: first negative electrode active material layer] The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer 22 to the initial charge capacity (A) of the positive electrode active material layer is 0.005 to 0.45. st From the open circuit voltage, Li / Li + The initial charge capacity of the first negative electrode active material layer 22 is determined by charging the first negative electrode active material layer 22 to a maximum charging voltage (2 nd From the open circuit voltage, Li / Li + It is determined by charging to 0.01V against

[0149] The maximum charging voltage is determined by the type of positive electrode active material. The maximum charging voltage may be, for example, 1.5 V, 2.0 V, 2.5 V, 3.0 V, 3.5 V, 4.0 V, 4.2 V, or 4.3 V. For example, Li 2 S or Li 2 The maximum charging voltage of the S-containing complex is Li / Li + For example, Li 2 S or Li 2 The maximum charging voltage of the S-containing complex is Li / Li + It may be 3.0 V. The ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer 22 to the initial charge capacity (A) of the positive electrode active material layer is, for example, 0.01 to 0.3, 0.01 to 0.2, or 0.05 to 0.1.

[0150] The initial charge capacity (mAh) of the positive electrode active material layer 12 is obtained by multiplying the charge specific capacity (mAh / g) of the positive electrode active material by the mass (g) of the positive electrode active material in the positive electrode active material layer 12. When multiple types of positive electrode active materials are used, the charge capacity density x mass value is calculated for each positive electrode active material, and the sum of these values ​​is the initial charge capacity of the positive electrode active material layer 12. The initial charge capacity of the first negative electrode active material layer 22 is also calculated in a similar manner. The initial charge capacity of the first negative electrode active material layer 22 is obtained by multiplying the charge capacity density (mAh / g) of the negative electrode active material by the mass of the negative electrode active material in the first negative electrode active material layer 22. When multiple types of negative electrode active materials are used, the charge capacity density x mass value is calculated for each negative electrode active material, and the sum of these values ​​is the initial charge capacity of the first negative electrode active material layer 22. The charge capacity density of each of the positive electrode active material and the negative electrode active material can be measured using an all-solid-state half-cell using lithium metal as a counter electrode. The initial charge capacity of each of the positive electrode active material layer 12 and the first negative electrode active material layer 22 is measured at a constant current density, for example, 0.1 mA / cm. 2 For the positive electrode, the measurement can be performed from the first open circuit voltage (OCV) to the maximum charging voltage, e.g., 3.0 V (vs. Li / Li + For the negative electrode, the measurements can be performed for an operating voltage from a second open circuit voltage (OCV) to 0.01 V relative to the negative electrode, e.g., lithium metal. For example, an all-solid-state half-cell having a positive electrode active material layer is charged at a constant current of 0.1 mA / cm2 from the first open circuit voltage to 3.0 V, and an all-solid-state half-cell having a first negative electrode active material layer is charged at a constant current of 0.1 mA / cm2 from the second open circuit voltage to 0.01 V. 2 The current density during constant current charging is, for example, 0.2 mA / cm 2 , or 0.5mA / cm 2The all-solid-state half-cell having the positive electrode active material layer can be charged, for example, from the first open circuit voltage to 2.5 V, 3.0 V, 3.5 V, or 4.0 V. The maximum charging voltage of the positive electrode active material layer can be determined by the maximum voltage of the battery that satisfies the safety conditions according to JISC8712:2015 of the Japanese Standards Association.

[0151] If the initial charge capacity of the first negative electrode active material layer 22 is excessively small, the thickness of the first negative electrode active material layer 22 becomes very thin, and lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode current collector 21 during repeated charge and discharge processes collapse the first negative electrode active material layer 22, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. If the charge capacity of the first negative electrode active material layer 22 increases excessively, the energy density of the all-solid-state secondary battery 1 decreases, and the internal resistance of the all-solid-state secondary battery 1 due to the first negative electrode active material layer 22 increases, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.

[0152] The thickness of the first negative electrode active material layer 22 is, for example, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less of the thickness of the positive electrode active material layer 12. The thickness of the first negative electrode active material layer 22 is, for example, 1 to 50%, 1 to 40%, 1 to 30%, 1 to 20%, 1 to 10%, or 1 to 5% of the thickness of the positive electrode active material layer 12. The thickness of the first negative electrode active material layer 22 is, for example, 1 μm to 20 μm, 2 μm to 15 μm, or 3 μm to 10 μm. If the thickness of the first negative electrode active material layer 22 is excessively thin, lithium dendrites formed between the first negative electrode active material layer 22 and the negative electrode current collector 21 collapse the first negative electrode active material layer 22, and the cycle characteristics of the all-solid-state secondary battery 1 are difficult to improve. If the thickness of the first negative electrode active material layer 22 increases excessively, the energy density of the all solid state secondary battery 1 decreases, and the internal resistance of the all solid state secondary battery 1 due to the first negative electrode active material layer 22 increases, making it difficult to improve the cycle characteristics of the all solid state secondary battery 1. If the thickness of the first negative electrode active material layer 22 decreases, for example, the initial charge capacity of the first negative electrode active material layer 22 also decreases.

[0153] [Negative electrode layer: second negative electrode active material layer] Although not shown, the all-solid-state secondary battery 1 further includes, for example, a second negative electrode active material layer disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 after charging. The second negative electrode active material layer is a metal layer containing lithium or a lithium alloy. The metal layer contains lithium or a lithium alloy. Therefore, since the second negative electrode active material layer is a metal layer containing lithium, it acts, for example, as a lithium reservoir. The lithium alloy is, for example, a Li-Al alloy, a Li-Sn alloy, a Li-In alloy, a Li-Ag alloy, a Li-Au alloy, a Li-Zn alloy, a Li-Ge alloy, a Li-Si alloy, etc., but is not limited thereto, and any alloy used as a lithium alloy in the art can be used. The second negative electrode active material layer is made of one of such alloys or lithium, or made of a plurality of alloys. The second negative electrode active material layer is, for example, a plated layer. The second negative electrode active material layer is deposited between the first negative electrode active material layer 22 and the negative electrode current collector 21 during charging of the all-solid-state secondary battery 1, for example.

[0154] The thickness of the second negative electrode active material layer is not particularly limited, and may be, for example, 1 μm to 500 μm, 1 μm to 200 μm, 1 μm to 150 μm, 1 μm to 100 μm, or 1 μm to 50 μm. If the thickness of the second negative electrode active material layer is too thin, it becomes difficult for the second negative electrode active material layer to perform the role of a lithium reservoir. If the thickness of the second negative electrode active material layer is too thick, the mass and volume of the all-solid-state secondary battery 1 increase, and the cycle characteristics of the all-solid-state secondary battery 1 may deteriorate.

[0155] Furthermore, in the all-solid-state secondary battery 1, the second negative electrode active material layer can be disposed, for example, between the negative electrode current collector 21 and the first negative electrode active material layer 22 before the all-solid-state secondary battery 1 is assembled. When the second negative electrode active material layer is disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 before the all-solid-state secondary battery 1 is assembled, the second negative electrode active material layer is a metal layer containing lithium, and therefore acts as a lithium reservoir. For example, lithium foil can be disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22 before the all-solid-state secondary battery 1 is assembled.

[0156] When the second negative electrode active material layer is precipitated by charging after the all-solid-state secondary battery 1 is assembled, the energy density of the all-solid-state secondary battery 1 increases because the all-solid-state secondary battery 1 does not include the second negative electrode active material layer when assembled. When the all-solid-state secondary battery 1 is charged, the first negative electrode active material layer 22 is charged beyond its charge capacity. That is, the first negative electrode active material layer 22 is overcharged. At the beginning of charging, lithium is absorbed in the first negative electrode active material layer 22. The negative electrode active material contained in the first negative electrode active material layer 22 forms an alloy or a compound with the lithium ions transferred from the positive electrode layer 10. When the first negative electrode active material layer 22 is charged beyond its capacity, for example, lithium is precipitated on the back surface of the first negative electrode active material layer 22, that is, between the negative electrode current collector 21 and the first negative electrode active material layer 22, and a metal layer corresponding to the second negative electrode active material layer is formed by the precipitated lithium. The second negative electrode active material layer is a metal layer mainly composed of lithium (that is, metallic lithium). Such a result can be obtained, for example, by the negative electrode active material contained in the first negative electrode active material layer 22 containing a material that forms an alloy or compound with lithium. During discharge, lithium in the first negative electrode active material layer 22 and the second negative electrode active material layer, i.e., the metal layer, is ionized and moves toward the positive electrode layer 10. Therefore, lithium can be used as the negative electrode active material in the all-solid-state secondary battery 1. In addition, since the first negative electrode active material layer 22 covers the second negative electrode active material layer, it serves as a protective layer for the second negative electrode active material layer, i.e., the metal layer, and also serves to suppress the deposition growth of lithium dendrites. Therefore, short-circuiting and capacity reduction of the all-solid-state secondary battery 1 are suppressed, and as a result, the cycle characteristics of the all-solid-state secondary battery 1 are improved. Furthermore, after the all-solid-state secondary battery 1 is assembled, when the second negative electrode active material layer is disposed by charging, the negative electrode layer 20, i.e., the negative electrode current collector 21 and the first negative electrode active material layer 22, and the region therebetween are Li-free regions that do not contain lithium (Li) in the initial state or after full discharge of the all-solid-state secondary battery 1.

[0157] [Negative electrode layer: negative electrode current collector] The negative electrode current collectors 21, 21a, 21b are made of a material that does not react with lithium, i.e., does not form any alloy or compound with lithium. The material constituting the negative electrode current collector 21 is, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), etc., but is not necessarily limited thereto, and any material used as an electrode current collector in the relevant technical field can be used. The negative electrode current collector 21 can be made of one of the above-mentioned metals, or an alloy or coating material of two or more metals. The negative electrode current collector 21 is, for example, in the form of a plate or foil.

[0158] The all-solid-state secondary battery 1 may further include, for example, a thin film containing an element that forms an alloy with lithium on one surface of the negative electrode current collector 21 (not shown). The thin film is disposed between the negative electrode current collector 21 and the first negative electrode active material layer 22. The thin film contains, for example, an element that forms an alloy with lithium. The element that forms an alloy with lithium is, for example, gold, silver, zinc, tin, indium, silicon, aluminum, bismuth, etc., but is not necessarily limited thereto, and any element that forms an alloy with lithium in the relevant technical field can be used. The thin film is made of one of these metals or an alloy of a plurality of metals. By disposing the thin film on one surface of the negative electrode current collector 21, for example, the deposition form of the second negative electrode active material layer deposited between the thin film 24 and the first negative electrode active material layer 22 is further flattened, and the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.

[0159] The thickness of the thin film is, for example, 1 nm to 800 nm, 10 nm to 700 nm, 50 nm to 600 nm, or 100 nm to 500 nm. If the thickness of the thin film is less than 1 nm, it is difficult for the thin film to exert its function. If the thickness of the thin film is excessively thick, the thin film itself may occlude lithium, the amount of lithium precipitated at the negative electrode may decrease, the energy density of the all-solid-state battery may decrease, and the cycle characteristics of the all-solid-state secondary battery 1 may decrease. The thin film may be disposed on the negative electrode current collector 21 by, for example, a vacuum deposition method, a sputtering method, a plating method, or the like, but is not necessarily limited to such a method, and any method for forming a thin film in the art may be used.

[0160] Although not shown, the negative electrode current collector 21 includes, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. The polymer may be an insulating polymer. When the base film includes an insulating thermoplastic polymer, the base film is softened or liquefied in the event of a short circuit, thereby cutting off the operation of the battery and suppressing a sudden increase in current. The metal layer may include, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), or an alloy thereof. The negative electrode current collector 21 may further include a metal piece and / or a lead tab. For more specific details regarding the base film, metal layer, metal piece, and lead tab of the negative electrode current collector 21, please refer to the above-mentioned positive electrode current collector 11. When the negative electrode current collector 21 has such a structure, the weight of the negative electrode can be reduced, and as a result, the energy density of the negative electrode and the lithium battery can be improved.

[0161] [Negative electrode layer: second inactive material] 6 to 9, the all-solid-state secondary batteries 1, 1a, and 1b further include second inactive members 50, 50a, 50b, and 50c disposed on the other surfaces of the negative electrode current collectors 21, 21a, and 21b.

[0162] The second inactive member 50 further includes a conductive material, and is thus distinguished from the first inactive member 40 in that it has electrical conductivity. The second inactive member 50 is, for example, a conductive flame-retardant inactive member.

[0163] The conductive material may be, for example, graphite, carbon black, acetylene black, Ketjen black, Denka black, carbon fiber, carbon nanotube (CNT), graphene, metal fiber, metal powder, etc. The electronic conductivity of the second inactive member 50 at 25° C. is, for example, 100 times or more, 1000 times or more, or 10000 times or more than the electronic conductivity of the first inactive member 40 at 25° C.

[0164] The second inactive member 50 includes, for example, a matrix, a filler, and a conductive material. The matrix includes, for example, a base material and a reinforcing material. The second inactive member 50 may further include a filler, a binder, and the like. The content of the conductive material included in the second inactive member 50 is, for example, 1 to 30 parts by weight, 1 to 20 parts by weight, 1 to 15 parts by weight, 1 to 10 parts by weight, 5 to 40 parts by weight, 5 to 30 parts by weight, or 5 to 35 parts by weight, relative to 100 parts by weight of the second inactive member 50.

[0165] The Young's modulus of the second inactive member 50 is, for example, smaller than that of the negative electrode current collector 21. The Young's modulus of the second inactive member 50 is, for example, 50% or less, 30% or less, 10% or less, or 5% or less of the Young's modulus of the negative electrode current collector 21. The Young's modulus of the second inactive member 50 is, for example, 0.01% to 50%, 0.1% to 30%, 0.1 to 10%, or 1 to 5% of the Young's modulus of the negative electrode current collector 21. The Young's modulus of the second inactive member 50 is, for example, 100 MPa or less, 50 MPa or less, 30 MPa or less, 10 MPa or less, or 5 MPa or less. The Young's modulus of the second inactive member 50 is, for example, 0.01 to 100 MPa, 0.1 to 50 MPa, 0.1 to 30 MPa, 0.1 to 10 MPa, or 1 to 5 MPa. The Young's modulus of the second inactive member 50 can be measured using a DMA (dynamic mechanical analyzer) or a UTM (universal testing machine). The Young's modulus of the second inactive member 50 can be measured according to ASTM D638.

[0166] Since the second inactive members 50, 50a, 50b have conductivity, they can fulfill the role of the negative electrode current collector 21. In addition, since the second inactive members 50, 50a, 50b have a lower Young's modulus than the negative electrode current collector 21, they can more effectively accommodate the volume change of the negative electrode layer 20 during charging and discharging of the all-solid-state secondary battery 1. As a result, the second inactive members 50, 50a, 50b can effectively relieve the internal stress caused by the volume change of the all-solid-state secondary battery 1 during charging and discharging of the all-solid-state secondary battery 1, and the cycle characteristics of the all-solid-state secondary battery 1 can be improved.

[0167] The thickness of the second inactive member 50 is, for example, greater than the thickness of the first negative electrode active material layer 22. The second inactive member 50 has a greater thickness than the first negative electrode active material layer 22, so that the volume change of the negative electrode layer 20 during charging and discharging can be accommodated more effectively. The thickness of the first negative electrode active material layer 22 is 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less of the thickness of the second inactive member 50. The thickness of the first negative electrode active material layer 22 is, for example, 1% to 50%, 1% to 40%, 1% to 30%, 1% to 20%, or 1% to 10% of the thickness of the second inactive member 50. The thickness of the second inactive member 50 is, for example, 1 μm to 300 μm, 10 μm to 300 μm, 50 μm to 300 μm, or 100 μm to 200 μm. If the thickness of the second inactive member 50 is excessively thin, it is difficult to provide the intended effect, and if the thickness of the second inactive member 50 is excessively thick, there is a possibility that the energy density of the all-solid-state secondary battery 1 will decrease. The form of the second inactive member 50 is not particularly limited and can be selected according to the form of the all-solid-state secondary battery 1. The second inactive member 50 may be, for example, in the form of a sheet, a rod, or a gasket.

[0168] The second inactive member 50 can be disposed, for example, on one or both surfaces of one all-solid-state secondary battery 1. The second inactive member 50 can be disposed, for example, between a plurality of stacked all-solid-state secondary batteries 1. The second inactive member 50 can be disposed, for example, between each of a plurality of stacked all-solid-state secondary batteries 1, on the top surface and / or the bottom surface.

[0169] The volume ratio and volume expansion rate of the all-solid-state secondary battery 1 before charging to the volume of the all-solid-state secondary battery 1 after charging may be, for example, 15% or less, 10% or less, or 5% or less. The volume of the all-solid-state secondary battery 1 before charging can be measured by measuring the thickness of the all-solid-state battery at 25°C before the chemical formation step. In addition, in the chemical formation step, the volume of the all-solid-state secondary battery 1 after charging can be measured by measuring the thickness of the all-solid-state battery at 25°C after the first charging step is completed.

[0170] The increase in volume of the negative electrode layer 20 during charging of the all-solid-state secondary battery 1 is offset by the decrease in volume of the positive electrode layer 10, and the second inactive member 50 accommodates the volume change of the negative electrode layer 20, thereby mitigating the volume change of the all-solid-state secondary battery 1 before and after charging.

[0171] The energy density per unit volume of the all-solid-state secondary battery 1 may be, for example, 500 to 900 Wh / L, 500 to 800 Wh / L, or 500 to 700 Wh / L. The energy density per unit weight of the all-solid-state secondary battery 1 may be, for example, 350 to 600 Wh / g, 350 to 580 Wh / g, 350 to 570 Wh / g, or 350 to 550 Wh / g. When the all-solid-state secondary battery 1 has an energy density in such a range, it is possible to provide an improved energy density compared to conventional secondary batteries.

[0172] [Solid electrolyte layer] [Solid electrolyte layer: solid electrolyte] 1-5, the solid electrolyte layer 30 (30a, 30b) includes an electrolyte disposed between the positive electrode layer 10 and the negative electrode layer 20. The electrolyte may include, for example, a solid electrolyte, a gel electrolyte, or a combination thereof.

[0173] The solid electrolyte can include, for example, a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a polymer solid electrolyte, or a combination thereof.

[0174] The solid electrolyte is, for example, a sulfide-based solid electrolyte. The sulfide-based solid electrolyte is, for example, Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiX (X is a halogen element), Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2, Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S5-LiI, Li 2 S.B. 2 S 3 , Li 2 SP 2 S 5 -ZmSn (m and n are positive numbers, Z is one of Ge, Zn or Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -LipMOq (p, q are positive numbers, M is one of P, Si, Ge, B, Al, Ga, and In), Li 7 -xPS 6 -xClx(0≦x≦2), Li 7 -xPS 6 -xBrx(0≦x≦2) and Li 7 -xPS 6 -xIx (0≦x≦2). The sulfide-based solid electrolyte is, for example, Li 2 S, P 2 S 5 The solid electrolyte is prepared by processing starting materials such as SiO2 and the like by a melt quenching method or a mechanical milling method. After such processing, a heat treatment can be performed. The solid electrolyte may be amorphous, crystalline, or a mixture thereof. The solid electrolyte may contain, for example, sulfur (S), phosphorus (P), and lithium (Li) as at least the constituent elements of the above-mentioned sulfide-based solid electrolyte material. For example, the solid electrolyte may contain Li 2 SP 2 S5 The sulfide-based solid electrolyte material for forming the solid electrolyte may be a material containing Li. 2 SP 2 S 5 If you use something that includes Li 2 S and P 2 S 5 The mixing molar ratio with Li 2 S:P 2 S 5 =The range is approximately 20:80~90:10, 25:75~90:10, 30:70~70:30, 40:60~60:40.

[0175] The sulfide-based solid electrolyte may include, for example, an Argyrodite-type solid electrolyte represented by the following Chemical Formula 1.

[0176] [ka]

[0177] In the above formula, A is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb, or Ta, X is S, Se, or Te, and Y is Cl, Br, I, F, CN, OCN, SCN, or N. 3 where 1≦n≦5 and 0≦x≦2. The sulfide-based solid electrolyte is, for example, Li 7-x P.S. 6-x Cl x (0≦x≦2), Li 7-x P.S. 6-x Br x (0≦x≦2) and Li 7-x P.S. 6-x I x (0≦x≦2). The sulfide-based solid electrolyte may be, for example, an argyrodite-type compound containing one or more selected from Li 6 P.S. 5 Cl, Li 6 P.S. 5 Br and Li 6 P.S. 5 The compound may be an argyrodite type compound containing one or more selected from I.

[0178] The density of the argyrodite-type solid electrolyte may be 1.5 to 2.0 g / cc. When the argyrodite-type solid electrolyte has a density of 1.5 g / cc or more, the internal resistance of the all-solid-state secondary battery is reduced, and penetration of the solid electrolyte layer by Li can be effectively suppressed.

[0179] The oxide-based solid electrolyte is, for example, Li 1+x+y Al x Ti 2-x S y P 3-y O 12 (0 <x<2、0≦y<3)、BaTiO 3 , Pb(Zr,Ti)O 3 (PZT), Pb 1-x La x Zr 1-y Ti y O 3 (PLZT)(0≦x<1, 0≦y<1), Pb(Mg 3 Nb 2 / 3 )O 3 -PbTiO 3 (PMN-PT), HfO 2 , SrTiO 3 , SnO 2 , CEO 2 , Na 2 O, MgO, NiO, CaO, BaO, ZnO, ZrO 2 , Y 2 O 3 , Al 2 O 3 , TiO 2 , SiO 2 , Li 3 PO 4 , Li x Ti y (PO 4 ) 3 (0 <x<2、0<y<3)、Li x Al y Ti z (PO 4 ) 3 (0 <x<2、0<y<1、0<z<3)、Li 1+x+y (Al, Ga) x(Ti, Ge) 2-x Si y P 3-y O 12 (0 ≦ x ≦ 1, 0 ≦ y ≦ 1), Li x La y TiO 3 (0 < x < 2, 0 < y < 3), Li 2 O, LiOH, Li 2 CO 3 , LiAlO 2 , Li 2 O - Al 2 O 3 -SiO 2 -P 2 O 5 -TiO 2 -GeO 2 , Li 3+x La 3 M 2 O 12 (M = Te, Nb, or Zr, 0 ≦ x ≦ 10), or combinations thereof may be used. The oxide-based solid electrolyte is produced, for example, by a sintering method or the like.

[0180] The oxide-based solid electrolyte is, for example, Li 7 La 3 Zr 2 O 12 (LLZO) and Li 3+x La 3 Zr 2-a M a O 12 (M doped LLZO, M = Ga, W, Nb, Ta, or Al, 0 < a < 2, 0 ≦ x ≦ 10) is a garnet-type solid electrolyte selected therefrom.

[0181] The polymer solid electrolyte may include, for example, a mixture of a lithium salt and a polymer, or may include a polymer having an ion-conducting functional group. The polymer solid electrolyte may be, for example, a polymer electrolyte that is in a solid state at 25° C. and 1 atm. The polymer solid electrolyte does not include, for example, a liquid. The polymer solid electrolyte includes a polymer, and the polymer is, for example, polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), poly(styrene-b-ethylene oxide) block copolymer (PS-PEO), poly(styrene-butadiene), poly(styrene-isoprene-styrene), poly(styrene-b-divinylbenzene) block copolymer, poly(styrene-ethylene oxide-styrene) block copolymer, polystyrene sulfonate ... Polyvinyl fluoride (PSS), Polymethyl methacrylate (PMMA), Polyethylene glycol (PEG), Polyacrylonitrile (PAN), Polytetrafluoroethylene (PTFE), Polyethylenedioxythiophene (PEDOT), Polypyrrole (PPY), Polyacrylonitrile (PAN), Polyaniline, Polyacetylene, Nafion, Aquivion, Flemion, Gore, Aciplex, Morgan ADP ADP), sulfonated poly(ether ether ketone) (SPEEK), sulfonated poly(arylene ether ketone ketone sulfone) (SPAEKKS), sulfonated poly(aryl ether ketone) (SPAEK), poly[bis(benzimidazobenzisoquinolinone)] (SPBIBI), polystyrene sulfonate (PSS), lithium 9,10-diphenylanthracene-2-sulfonate (DPASLi + ) or a combination thereof, but is not limited thereto, and any can be used as long as it is used as a polymer electrolyte in the art. The lithium salt can be any used as long as it is used as a lithium salt in the art. The lithium salt can be, for example, LiPF 6 , LiBF 4 , LiSbF6 , LiAsF 6 , LiClO 4 , LiCF 3 SO 3 , Li(CF 3 SO 2 ) 2 N, LiC 4 F 9 SO 3 , LiAlO 2 , LiAlCl 4 , LiN(C x F 2x+1 SO 2 )(C y F 2y+1 SO 2 ) (x and y are each 1 to 20), LiCl, LiI, or a mixture thereof. The polymer contained in the polymer solid electrolyte may be, for example, a compound containing 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The weight average molecular weight of the polymer contained in the polymer solid electrolyte may be, for example, 1000 Dalton or more, 10,000 Dalton or more, 100,000 Dalton or more, or 1,000,000 Dalton or more.

[0182] The gel electrolyte includes, for example, a polymer gel electrolyte. The gel electrolyte can, for example, not include a polymer and have a gel state.

[0183] The polymer gel electrolyte may, for example, include a liquid electrolyte and a polymer, or may include an organic solvent and a polymer having an ion-conducting functional group. The polymer gel electrolyte may, for example, be a polymer electrolyte that is in a gel state at 25° C. and 1 atm. The polymer gel electrolyte may, for example, be free of liquid and in a gel state. The liquid electrolyte used in the polymer gel electrolyte may, for example, be an ionic liquid, a mixture of a lithium salt and an organic solvent, a mixture of a lithium salt and an organic solvent, a mixture of an ionic liquid and an organic solvent, or a mixture of a lithium salt, an ionic liquid, and an organic solvent. The polymer used in the polymer gel electrolyte may be selected from among the polymers used in the solid polymer electrolyte. The organic solvent may be selected from among the organic solvents used in the liquid electrolyte. The lithium salt may be selected from among the lithium salts used in the solid polymer electrolyte. The ionic liquid has a melting point below room temperature, is composed of only ions, and refers to a salt that is in a liquid state at room temperature or a room temperature molten salt. The ionic liquid may, for example, comprise: a) one or more cations selected from ammonium, pyrrolidinium, pyridinium, pyrimidinium, imidazolium, piperidinium, pyrazolium, oxazolium, pyridazinium, phosphonium, sulfonium, triazolium, and mixtures thereof; and b) BF 4 - , P.F. 6 - , AsF 6 - , SbF 6 - , AlCl 4 - , HSO 4 - , ClO 4 - , C.H. 3 SO 3 - , C.F. 3 CO 2 - , Cl - , Br - , I - , S.O. 4 - , C.F. 3 SO 3- , (FSO 2 ) 2 N - , (C 2 F 5 SO 2 ) 2 N - , (C 2 F 5 SO 2 )(CF 3 SO 2 )N - , and (CF 3 SO 2 ) 2 N and one or more anions selected from the group consisting of a compound containing one or more anions selected from N. The polymer solid electrolyte can be impregnated with a liquid electrolyte in a secondary battery to form a polymer gel electrolyte. The polymer gel electrolyte can further include inorganic particles. The polymer contained in the polymer gel electrolyte can be, for example, a compound containing 10 or more, 20 or more, 50 or more, or 100 or more repeating units. The weight average molecular weight of the polymer contained in the polymer gel electrolyte can be, for example, 500 Dalton or more, 1000 Dalton or more, 10,000 Dalton or more, 100,000 Dalton or more, or 1,000,000 Dalton or more.

[0184] The solid electrolyte layer 30 may be impermeable to lithium polysulfide. Therefore, it is possible to block a side reaction between the negative electrode layer and lithium polysulfide generated during charging and discharging of the sulfide-based positive electrode active material, and therefore it is possible to improve the cycle characteristics of the all-solid-state secondary battery 1 including the solid electrolyte layer 30.

[0185] [Solid electrolyte layer: binder] The solid electrolyte layer 30 may contain, for example, a binder. The binder contained in the solid electrolyte layer 30 is, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited thereto, and any binder used as a binder in the relevant technical field can be used. The binder of the solid electrolyte layer 30 may be the same as or different from the binder contained in the positive electrode active material layer 12 and the first negative electrode active material layer 22. The binder can be omitted.

[0186] The binder content in the solid electrolyte layer 30 is 0.1 to 10 wt %, 0.1 to 5 wt %, 0.1 to 3 wt %, 0.1 to 1 wt %, 0 to 0.5 wt %, or 0 to 0.1 wt % based on the total weight of the solid electrolyte layer 30. EXAMPLES

[0187] The present invention will be described in more detail with reference to the following examples and comparative examples, however, the examples are intended to illustrate the present invention and are not intended to limit the scope of the present invention.

[0188] Production example 1: Li 2 S-LiI-AlI 3 -CNF complex (First Stage) LiI and AlI 3 In a 1:1 molar ratio, a first mixture was prepared.

[0189] Li 2 The second mixture was prepared by mixing S with the first mixture in a weight ratio of 40:20. The second mixture was mechanically milled using a ball mill to obtain Li 2 S-LiI-AlI 3 The composite was produced. The milling conditions were 25°C, 600 rpm, and 10 hours. The milling energy applied to the sample during milling was 28 G.

[0190] (Second Stage) Li 2 S-LiI-AlI 3 The composite and carbon nanofibers (CNF) were mixed in a weight ratio of 60:10 to prepare the third mixture. The third mixture was mechanically milled using a ball mill to obtain Li 2 S-LiI-AlI 3 A Li-CNF composite was produced. The milling conditions were 25°C, 600 rpm, and 10 hours. The milling energy applied to the sample during milling was 28 G. 2 S-LiI-AlI 3 The -CNF composite was used as a sulfide-based positive electrode active material.

[0191] Reference production example 1: Li 2 S, LiI, and AlI 3 and CNF mixture LiI and AlI 3 In a 1:1 molar ratio, a first mixture was prepared.

[0192] Li 2 S and the first mixture were mixed in a weight ratio of 40:20, and such Li 2 S, LiI, and AlI 3 The mixture was further mixed with carbon nanofibers (CNF) in a weight ratio of 60:10 and used as a sulfide-based positive electrode active material.

[0193] Example 1: Mono-cell all-solid-state secondary battery, sulfide-based positive electrode active material (Li2S-CNF composite), flame-retardant first inert member (Production of negative electrode layer) A 10 μm thick SUS foil was prepared as a negative electrode current collector, and carbon black (CB) with a primary particle size of about 30 nm and silver (Ag) particles with an average particle diameter of about 60 nm were prepared as a negative electrode active material.

[0194] 4g of mixed powder, which was a mixture of carbon black (CB) and silver (Ag) particles in a weight ratio of 3:1, was placed in a container, and 4g of an NMP solution containing 7% by weight of PVDF binder (Kureha's #9300) was added to prepare a mixed solution. Next, the mixed solution was stirred while adding NMP little by little to prepare a slurry. The prepared slurry was applied to a SUS sheet using a bar coater and dried in air at 80°C for 10 minutes. The resulting laminate was vacuum dried at 40°C for 10 hours. The dried laminate was then dried at 5 ton f / cm 2 The surface of the first negative electrode active material layer of the laminate was flattened by cold roll pressing at a speed of 5 m / sec under a pressure of 1000 MPa. The negative electrode layer was produced by the above process. The thickness of the first negative electrode active material layer included in the negative electrode layer was about 15 μm. The area of ​​the first negative electrode active material layer and the negative electrode current collector were the same. The initial charge capacity of the negative electrode was measured using the above-mentioned half-cell. The initial charge capacity of the first negative electrode active material layer was 2.3 mAh.

[0195] (Production of the positive electrode layer) Li as the positive electrode active material 2 S-CNF composites were prepared. 2 The S-CNF composite was prepared by the method disclosed in Electrochimica Acta 230 (2017) 279-284, except that VGCF (vapor grown carbon fiber) was replaced with CNF (carbon nanofiber). 6 P.S. 5 Cl (D50=3.0μm, crystalline) was prepared. Ketjen black was prepared as a conductive agent. These materials were mixed in a weight ratio of positive electrode active material: solid electrolyte: conductive agent=40:50:10 to prepare a positive electrode mixture. The positive electrode mixture was obtained by dry mixing using a ball mill. The positive electrode mixture obtained by ball milling formed an ionically conductive and electronically conductive network.

[0196] The positive electrode mixture was placed on one side of a positive electrode current collector made of aluminum foil or SUS with one side carbon coated, and plate pressed for 10 minutes at a pressure of 200 MPa to prepare a positive electrode layer. The thickness of the positive electrode layer was about 120 μm. The thickness of the positive electrode active material layer was about 100 μm, and the thickness of the carbon-coated aluminum foil was about 20 μm. The areas of the positive electrode active material layer and the positive electrode current collector were the same.

[0197] The initial charge capacity of the positive electrode was measured using the half-cell described above. The initial charge capacity of the positive electrode active material layer was 25 mAh.

[0198] In Example 1, the ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer is 0.09. The initial charge capacity of the positive electrode active material layer is calculated from the first open circuit voltage as follows: Li / Li + The initial charge capacity of the first negative electrode active material layer was determined by charging to 2.8 V against Li / Li from the second open circuit voltage. + The initial charge capacity (B) of the first negative electrode active material layer and the initial charge capacity (A) of the positive electrode active material layer were determined by charging to 0.01 V vs. V. In Examples 2 to 8 and Comparative Example 1, the ratios (B / A) of the initial charge capacity (B) of the first negative electrode active material layer and the initial charge capacity (A) of the positive electrode active material layer, measured under the same conditions as in Example 1, were 0.07 to 0.09, respectively. In Examples 7 and 8, double-sided positive electrodes were used, and therefore half of the initial positive electrode charge capacity was used in calculating the ratio (B / A).

[0199] (Manufacturing of solid electrolyte layer) Argyrodite-type crystals Li 6 P.S. 5A mixture was prepared by adding 1.5 parts by weight of an acrylic binder to 98.5 parts by weight of the solid electrolyte Cl solid electrolyte (D50=3.0 (m, crystalline). Octyl acetate was added to the mixture and stirred to prepare a slurry. The prepared slurry was applied to a 15 μm-thick nonwoven fabric placed on a 75 μm-thick PET substrate using a bar coater, and dried in air at 80° C. for 10 minutes to obtain a laminate. The obtained laminate was vacuum-dried at 80° C. for 2 hours. A solid electrolyte layer was manufactured by the above process.

[0200] (Flame-retardant inactive material) Pulp fiber, glass fiber, aluminum hydroxide (Al(OH) 3 ), an acrylic binder and a solvent were mixed to form a slurry into a gasket shape, and the solvent was then removed to produce a flame-retardant inert member.

[0201] Pulp fiber, glass fiber, aluminum hydroxide (Al(OH) 3 The weight ratio of the inert material to the acrylic binder was 20:8:70:2. The thickness of the inert material was 120 μm.

[0202] Before being placed on the solid electrolyte layer, the manufactured flame-retardant inert member was vacuum heat-treated at 80° C. for 5 hours to remove moisture and the like from the flame-retardant inert member.

[0203] (Manufacturing all-solid-state secondary batteries) Referring to FIG. 1, a solid electrolyte layer was disposed on the negative electrode layer such that the first negative electrode active material layer was in contact with the solid electrolyte layer, and a positive electrode layer was disposed on the solid electrolyte layer. A gasket was disposed around the positive electrode layer to surround the positive electrode layer and to contact the solid electrolyte layer, to prepare a laminate. The gasket had a thickness of about 120 μm. A flame-retardant inert material was used as the gasket. The gasket was disposed so as to contact the side of the positive electrode layer and the solid electrolyte layer. The positive electrode layer was disposed at the center of the solid electrolyte layer, and the gasket was disposed so as to surround the positive electrode layer and extend to the end of the solid electrolyte layer. The area of ​​the positive electrode layer was about 90% of the area of ​​the solid electrolyte layer, and the gasket was disposed over the entire remaining 10% area of ​​the solid electrolyte layer where the positive electrode layer was not disposed.

[0204] The prepared laminate was subjected to plate pressing at 85°C and a pressure of 500 MPa for 30 minutes. Such pressing sinters the solid electrolyte layer, improving the battery characteristics. The thickness of the sintered solid electrolyte layer was about 45 μm. The density of the Li6PS5Cl solid electrolyte, which is an argyrodite-type crystal contained in the sintered solid electrolyte layer, was 1.6 g / cc. The area of ​​the solid electrolyte layer was the same as that of the negative electrode layer.

[0205] The pressurized laminate was placed in a pouch and vacuum sealed to manufacture an all-solid-state secondary battery. A portion of the positive electrode current collector and a portion of the negative electrode current collector were extended outside the sealed battery to be used as a positive electrode layer terminal and a negative electrode layer terminal.

[0206] Example 2: Sulfide-based positive electrode active material (Li 2 S-CNF composite), flame-retardant first inert material, conductive flame-retardant second inert material An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that a sheet-shaped conductive flame-retardant member having the same area and shape as the laminate was additionally disposed on the negative electrode current collector of the pressed laminate before the pressed laminate was placed in a pouch, and the all-solid-state secondary battery was manufactured by vacuum sealing. The conductive flame-retardant inert member sheet was prepared as follows.

[0207] The conductive, flame retardant, inert material sheet can act as a resilient sheet.

[0208] (Conductive flame-retardant inert material) Pulp fiber, glass fiber, aluminum hydroxide (Al(OH) 3 The flame-retardant inert member was manufactured by forming a slurry of a mixture of cellulose fiber, glass fiber, aluminum hydroxide (Al(OH) 3 The weight ratio of the conductive material, acrylic binder, and conductive material was 20:8:50:2:20. The conductive flame-retardant inert member had a thickness of 120 μm. The conductive flame-retardant inert member thus manufactured was vacuum heat-treated at 80° C. for 5 hours before being placed on the negative electrode current collector to remove moisture and other substances from the conductive flame-retardant inert member.

[0209] Example 3: Sulfide-based positive electrode active material (Li 2 S-CNF composite), non-flame retardant first inert material An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the flame-retardant inert member was changed to a non-flame-retardant inert member.

[0210] The non-flame retardant inert material contains pulp fiber and acrylic binder in a weight ratio of 98:2, glass fiber and Al(OH) 3 The thickness of the non-flame retardant inert member was 120 μm.

[0211] Example 4: Sulfide-based positive electrode active material (Li 2 SC-Li6PS5Cl complex), flame-retardant first inert material Li as the positive electrode active material 2 Instead of the S-VGCF complex, Li 2 SC-Li 6 P.S. 5 An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the Cl complex was used.

[0212] Li 2 SC-Li 6 P.S. 5The Cl complex was prepared by the method disclosed in Nano Lett. 2016, 16, 7, 4521-4527.

[0213] Example 5: Sulfide-based positive electrode active material (Li 2 SC composite), first negative electrode active material layer (Ag-supported carbon), flame-retardant first inactive material, conductive flame-retardant second inactive material An all-solid-state secondary battery was manufactured in the same manner as in Example 2, except that the negative electrode active material was a carbon black carrying silver particles, instead of a mixture of carbon black and silver particles.

[0214] (Production of Silver Particle-Supported Carbon Black) Carbon black was dispersed in a 1.0 M sulfuric acid solution, stirred for 2 hours, filtered and dried to prepare acid-treated carbon black.

[0215] 10 g of acid-treated carbon black was added to a mixed solvent of 1500 g of distilled water, 1500 g of ethanol, and 30 g of glycerol, and then the mixture was stirred. AgNO 3 A mixed solution was prepared by adding 2 g of carbon black and stirring. The particle size of the carbon black was 80 nm. A reducing agent was added to the mixed solution to reduce and support the silver ions on the carbon black. The carbon black supporting the silver-containing particles was filtered, washed and dried to prepare a composite negative electrode active material. Measurements using a scanning electron microscope and XPS confirmed that multiple silver-containing particles were supported on the carbon black particles. The silver-containing particles consisted of silver particles, silver oxide (Ag 2 O) particles, and silver (Ag) and silver oxide (Ag 2 O). The content of silver-containing particles in the composite negative electrode active material was 5 wt %. The average particle size of the silver particles was 10 nm.

[0216] Example 6: Sulfide-based positive electrode active material (Li 2 S-CNF-LiI composite), flame-retardant first inert material Li as the positive electrode active material 2 Instead of the S-CNF complex, Li 2 An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the SC-LiI composite was used.

[0217] Li 2 The SC-LiI complex is 6 P.S. 5 This was produced by the method disclosed in Nano Lett. 2016, 16, 7, 4521-4527, except that Cl was replaced with LiI.

[0218] Comparative example 1: Sulfide-based positive electrode active material, no inert material used (free) An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that a flame-retardant inactive member (ie, a gasket) was not used during the manufacture of the all-solid-state secondary battery.

[0219] Comparative Example 2: Oxide-based positive electrode active material, flame-retardant first inactive member Li 2 An all-solid-state secondary battery was produced in the same manner as in Example 1, except that a positive electrode containing a lithium transition metal oxide was used instead of the positive electrode containing the S positive electrode active material.

[0220] In Comparative Example 2, the ratio (B / A) of the initial charge capacity (B) of the first negative electrode active material layer to the initial charge capacity (A) of the positive electrode active material layer is 0.09. The initial charge capacity of the positive electrode active material layer is calculated from the first open circuit voltage as follows: Li / Li + The initial charge capacity of the first negative electrode active material layer was determined by charging to 4.25 with respect to the second open circuit voltage. + The capacitance was determined by charging to 0.01 V relative to the

[0221] A positive electrode comprising a lithium transition metal oxide was prepared in the following manner.

[0222] (Production of the positive electrode layer) Li as the positive electrode active material 2 O-ZrO 2 (LZO) coated LiNi 0.8 Co 0.15 Al 0.05 O 2The LZO-coated positive electrode active material was prepared according to the method disclosed in Korean Patent Publication No. 10-2016-0064942. The solid electrolyte was Li 6 P.S. 5 Cl (D50=0.5μm, crystalline) was prepared. Polytetrafluoroethylene (PTFE) binder (DuPont's Teflon binder) was prepared as a binder. Carbon nanofibers (CNF) were prepared as a conductive agent. Such materials were mixed with xylene solvent in a weight ratio of 84:11.5:3:1.5 of positive electrode active material: solid electrolyte: conductive material: binder, and the mixture was formed into a sheet shape, and then vacuum dried at 40°C for 8 hours to prepare a positive electrode sheet. The positive electrode sheet was placed on one side of a positive electrode current collector made of aluminum foil coated with carbon on one side, and plate pressed for 10 minutes at a pressure of 200MPa to prepare a positive electrode layer. The thickness of the positive electrode layer was about 120μm. The thickness of the positive electrode active material layer was about 100μm, and the thickness of the carbon-coated aluminum foil was about 20μm. The areas of the positive electrode active material layer and the positive electrode current collector were the same.

[0223] Example 7: One bi-cell all-solid-state secondary battery, sulfide-based positive electrode active material (Li 2 S-CNF composite), flame-retardant first inactive material (Manufacturing bi-cell all-solid-state secondary batteries) The positive electrode layer was prepared in the same manner as in Example 1, except that the positive electrode active material layers were disposed on both sides of the positive electrode current collector.

[0224] The total thickness of the positive electrode layers was about 220 μm, the thicknesses of the positive electrode active material layers were each about 100 μm, and the thickness of the carbon-coated aluminum foil was about 20 μm.

[0225] Two negative electrode layers, two solid electrolyte layers, and two flame-retardant inactive members were prepared in the same manner as in Example 1.

[0226] Referring to FIG. 3, a solid electrolyte layer was disposed on the negative electrode layer such that the first negative electrode active material layer was in contact with the solid electrolyte layer, and a positive electrode layer was disposed on the solid electrolyte layer. The positive electrode layer had a structure in which a positive electrode active material layer was disposed on each side of a positive electrode current collector. A gasket was disposed around the positive electrode layer so as to surround the positive electrode layer and to be in contact with the solid electrolyte layer. The gasket had a thickness of about 220 μm. The gasket may have a structure in which two gaskets each having a thickness of 110 μm are laminated, or one gasket having a thickness of 220 μm. A flame-retardant inert material was used as the gasket.

[0227] The gasket was arranged so as to contact the side of the positive electrode layer and the solid electrolyte layer. The positive electrode layer was arranged at the center of the solid electrolyte layer, and the gasket was arranged to surround the positive electrode layer and extend to the end of the solid electrolyte layer. The area of ​​the positive electrode layer was about 90% of the area of ​​the solid electrolyte layer, and the gasket was arranged over the remaining 10% area of ​​the solid electrolyte layer where the positive electrode layer was not arranged. A stack was produced by placing the solid electrolyte layer on the positive electrode layer and the gasket, and placing the negative electrode layer on the solid electrolyte layer.

[0228] The prepared laminate was subjected to plate pressing at 85°C and a pressure of 500 MPa for 30 minutes. Such pressing sinters the solid electrolyte layer, improving the battery characteristics. The thickness of one sintered solid electrolyte layer was about 45 μm. The density of the Li6PS5Cl solid electrolyte, which is an argyrodite-type crystal contained in the sintered solid electrolyte layer, was 1.6 g / cc. The area of ​​the solid electrolyte layer was the same as that of the negative electrode layer.

[0229] The pressurized laminate was placed in a pouch and vacuum sealed to produce an all-solid-state secondary battery. A portion of the positive electrode current collector and a portion of the negative electrode current collector were extended outside the sealed battery to be used as a positive electrode layer terminal and a negative electrode layer terminal.

[0230] Example 8: Bi-cell all-solid-state secondary battery, sulfide-based positive electrode active material (Li2S-CNF composite), flame-retardant first inactive member, conductive flame-retardant second inactive member An all-solid-state secondary battery was manufactured in the same manner as in Example 7, except that a sheet-shaped conductive flame-retardant inert member having the same area and shape as the laminate was additionally disposed on one side of the pressed laminate and the other side opposite to the one side before the pressed laminate was placed in the pouch, and then vacuum-sealed to manufacture an all-solid-state secondary battery. The conductive flame-retardant inert member was prepared in the same manner as in Example 2.

[0231] Example 9: Mono-cell all-solid-state secondary battery, sulfide-based positive electrode active material (Li 2 S-LiI-AlI 3 -CNF composite), flame-retardant first inactive material Li as the positive electrode active material 2 Instead of the S-CNF composite, the Li 2 S-LiI-AlI 3 An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the -CNF composite was used.

[0232] Reference example 1: Mono-cell all-solid-state secondary battery, sulfide-based positive electrode active material (Li 2 S-LiI-AlI 3 -CNF mixture), flame retardant first inert member Li as the positive electrode active material 2 Instead of the S-CNF composite, Li produced in Reference Production Example 1 was used. 2 S, LiI, and AlI 3 An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that a simple mixture of ZnO and CNF was used.

[0233] Evaluation example 1: Calculation of volume change rate during charging of all-solid-state secondary batteries [Al current collector (10 μm) / LiNi 0.8 Co 0.15 Al 0.05 O 2 (NCA) Positive electrode active material layer (100μm) / Li 6 P.S. 5The volume change of the first all-solid-state secondary battery during charging was calculated from the initial first volume of the first all-solid-state secondary battery having a structure of NCA solid electrolyte layer (32 μm) / first negative electrode active material layer (7 μm) / SUS current collector (10 μm) and the second volume after charging of the first all-solid-state secondary battery in which a lithium metal layer of 30 μm in thickness was deposited between the first negative electrode active material layer and the SUS current collector by charging, and is shown in the following Table 1. It was assumed that there was no change in the thickness of the NCA positive electrode active material layer before and after charging.

[0234] [Al current collector (10 μm) / Li 2 S(60wt%)-Carbon(40wt%) Positive electrode active material layer (50μm) / Li 6 P.S. 5 The volume change of the second all-solid-state secondary battery during charging was calculated from the initial first volume of the second all-solid-state secondary battery having a structure of (1) LiCl solid electrolyte layer (32 μm) / 1st negative electrode active material layer (7 μm) / SUS current collector (10 μm) and the second volume after charging of the second all-solid-state secondary battery in which a lithium metal layer of 30 μm thickness was deposited between the first negative electrode active material layer and the SUS current collector by charging, and is shown in Table 1 below. 2 It was assumed that the thickness of the S(60wt%)-C(40wt%) composite was reduced by 15μm from 50μm to 35μm. 2 It was assumed that all the lithium contained in S moves to the negative electrode. The positive electrode active material layer of the second all-solid-state secondary battery is Li 2 It was assumed to consist only of S and carbon. The positive electrode active material layer of the first all-solid-state secondary battery was assumed to consist of NCA.

[0235] [Table 1]

[0236] As shown in Table 1, Li 2In the second all-solid-state secondary battery having a positive electrode active material layer containing S, the volume of the negative electrode layer increases due to the precipitation of the lithium metal layer, but the volume of the positive electrode active material layer decreases, suppressing the increase in the volume of the all-solid-state secondary battery as a whole. In contrast, in the first all-solid-state secondary battery having a positive electrode active material layer containing a lithium transition metal oxide, the volume change of the positive electrode active material layer is negligible, and therefore the increase in the volume of the all-solid-state secondary battery as a whole due to the precipitation of the lithium metal layer is remarkable.

[0237] Therefore, it was confirmed that the second all-solid-state secondary battery effectively prevents deterioration of the all-solid-state secondary battery, such as cracks, by mitigating the volume change that occurs during charging and discharging of the all-solid-state secondary battery through the first all-solid-state secondary battery.

[0238] Evaluation Example 2: Evaluation Example 2: XRD analysis and scanning electron microscope analysis Raw material (bare) Li used in Production Example 1 2 S, crushed Li 2 S, and Li produced in Production Example 1 2 S-LiI-AlI 3 The XRD spectrum was measured for the Li-CNF composite using CuKα radiation. The results are shown in Table 1. 2 The first peak for the (111) crystal plane of S is 2 The size and lattice constant of the S crystallite were derived.

[0239] Crushed Li 2 S is Li in the first step of Example 1. 2 S and the first mixture (LiI and AlI 3 1:1 molar mixture of Li 2 The milling was carried out under the same conditions, except that the weight of S was changed to 50 parts by weight. The second step was not carried out.

[0240] Raw material Li used in Production Example 1 2 S, crushed Li 2 S, and Li produced in Production Example 1 2 S-LiI-AlI 3The particle size of the composite (i.e., D50 particle size) and the Li of the composite were measured using a laser particle size analyzer (PSA) and a scanning electron microscope. 2 The particle size was measured and the results are shown in Table 2 below.

[0241] [Table 2]

[0242] As shown in Table 2, Li 2 S-LiI-AlI 3 The Li2S particle size and Li 2 S crystallite size is bare Li 2 was significantly decreased compared to S.

[0243] Although not shown in Table 2, Li of Production Example 1 2 S-LiI-AlI 3 Li-CNF composite 2 The S lattice constant is bare Li 2 It is even larger than the lattice constant of S.

[0244] Bare Li 2 The lattice constant of Li compared to S 2 S-LiI-AlI 3 Li-CNF composite 2 The increase in the S lattice constant is due to the 2 LiI and / or AlI in S crystal 3 It was determined that this was because Li was dissolved. 2 S-LiI-AlI 3 Li in the -CNF composite 2 S and LiI and / or AlI 3 Although not shown in Table 2, it was confirmed that Li produced in Production Example 1 formed a solid solution. 2 S-LiI-AlI 3 The particle size of the -CNF composite was approximately 5 μm.

[0245] Evaluation example 3: Charge / discharge test The charge / discharge characteristics of the all-solid-state secondary batteries prepared in Examples 1 to 9 and Comparative Example 1 were evaluated by the following charge / discharge test. The charge / discharge test was performed by placing the all-solid-state secondary batteries in a thermostatic chamber at 45°C.

[0246] In the first cycle, the battery was charged at a constant current of 0.1 C for 12.5 hours until the battery voltage reached 2.5 V to 2.8 V. Then, the battery was discharged at a constant current of 0.1 C for 12.5 hours until the battery voltage reached 0.5 V.

[0247] In the second cycle, the battery was charged at a constant current of 0.33 C for 12.5 hours until the battery voltage reached 2.5 V to 2.8 V. Then, the battery was discharged at a constant current of 0.33 C for 12.5 hours until the battery voltage reached 0.5 V.

[0248] In the third cycle, the battery was charged at a constant current of 1.0 C for 12.5 hours until the battery voltage reached 2.5 V to 2.8 V. Then, the battery was discharged at a constant current of 1.0 C for 12.5 hours until the battery voltage reached 0.5 V.

[0249] The charge / discharge characteristics of the all-solid-state secondary battery prepared in Comparative Example 2 were evaluated by the following charge / discharge test. The charge / discharge test was performed by placing the all-solid-state secondary battery in a thermostatic chamber at 45°C.

[0250] In the first cycle, the battery was charged at a constant current of 0.1 C for 12.5 hours until the battery voltage reached 3.9 V to 4.25 V. Then, the battery was discharged at a constant current of 0.1 C for 12.5 hours until the battery voltage reached 2.5 V.

[0251] In the second cycle, the battery was charged at a constant current of 0.33 C for 12.5 hours until the battery voltage reached 3.9 V to 4.25 V. Then, the battery was discharged at a constant current of 0.33 C for 12.5 hours until the battery voltage reached 2.5 V.

[0252] In the third cycle, the battery was charged at a constant current of 1.0 C for 12.5 hours until the battery voltage reached 3.9 V to 4.25 V. Then, the battery was discharged at a constant current of 1.0 C for 12.5 hours until the battery voltage reached 2.5 V.

[0253] The presence or absence of short circuits during the charge / discharge process up to the third cycle, the initial discharge capacity, and the high rate characteristics are shown in Table 3 below.

[0254] The presence or absence of a short circuit is indicated by an O if a short circuit occurs before the completion of the first cycle, a △ if a short circuit occurs in the second cycle, and an X if a short circuit does not occur until the completion of the third cycle.

[0255] [Table 3]

[0256] As shown in Table 3, the all-solid-state secondary batteries of Examples 1 to 9 exhibited improved cycle characteristics compared to the all-solid-state secondary battery of Comparative Example 1.

[0257] Evaluation example 4: High temperature life characteristic test The charge / discharge characteristics of the all-solid-state secondary batteries prepared in Examples 1 to 9, Comparative Example 1, and Reference Example 1 were evaluated by the following charge / discharge test.

[0258] The charge / discharge test was carried out by placing the all-solid-state secondary battery in a thermostatic chamber at 45°C.

[0259] In the first cycle, the battery was charged at a constant current of 0.6 mA / cm2 for 12.5 hours until the battery voltage reached 2.5 V to 2.8 V. Then, the battery was discharged at a constant current of 0.6 mA / cm2 for 12.5 hours until the battery voltage reached 0.5 V.

[0260] The charge / discharge characteristics of the all-solid-state secondary battery prepared in Comparative Example 2 were evaluated by the following charge / discharge test. The charge / discharge test was performed by placing the all-solid-state secondary battery in a thermostatic chamber at 45°C.

[0261] The first cycle is 0.6 mA / cm until the battery voltage reaches 3.9 V to 4.25 V. 2 The battery was charged for 12.5 hours at a constant current of 0.6 mA / cm until the battery voltage reached 2.5 V. 2 Discharge was carried out at a constant current of 1000 V for 12.5 hours.

[0262] The discharge capacity of the first cycle was taken as the standard capacity. From the second cycle onwards, charging and discharging were carried out up to 150 cycles under the same conditions as the first cycle. The measurement results are shown in Table 3 below.

[0263] The more cycles required for the discharge capacity to decrease to 95% of the standard capacity from the second cycle, the better the life characteristics were considered to be.

[0264] In the all-solid-state secondary battery of Comparative Example 1, a short circuit occurred before the first cycle was completed, making it impossible to measure the life characteristics.

[0265] [Table 4]

[0266] As shown in Table 4, the all-solid-state secondary batteries of Examples 1 to 8 had improved life characteristics compared to the all-solid-state secondary battery of Comparative Example 2.

[0267] The all-solid-state secondary battery of Example 6 is Li 2 By including the SC-LiI composite as the positive electrode active material, Li 2 Example 1, which contains the SC composite, and Li 2 SC-Li 6 P.S. 5 The life characteristics were further improved as compared to Example 4, which contained a Cl complex.

[0268] Li 2 The all-solid-state secondary batteries of Examples 1 to 6 containing S were determined to have improved life characteristics due to less volume change during charging and discharging compared to the all-solid-state secondary battery of Comparative Example 2 containing an oxide-based positive electrode active material.

[0269] The all-solid-state secondary batteries of Examples 7 and 8, which have a bi-cell structure in which components are symmetrically arranged, were determined to have improved life characteristics by effectively mitigating volume changes during charging and discharging, compared to the all-solid-state secondary batteries of Examples 1 to 4, which have a mono-cell structure.

[0270] It was determined that the all-solid-state secondary batteries of Examples 1, 2 and 4, which contain a flame-retardant inert member, have improved life characteristics compared to Example 3, which contains a non-flame-retardant inert member.

[0271] The all-solid-state secondary battery of Example 8 was determined to have improved life characteristics compared to the all-solid-state secondary battery of Example 7 because the second inactive member was additionally disposed on the negative electrode current collector, effectively alleviating the stress of the negative electrode layer where volume change is concentrated. For the same reason, the all-solid-state secondary battery of Example 2 was determined to have improved life characteristics compared to Examples 1, 3, and 4. The all-solid-state secondary battery of Example 5 was determined to have improved life characteristics compared to Example 2, which is a simple mixture of silver particles and carbon particles, by using carbon carrying silver particles.

[0272] Although not shown in Table 4, the life characteristics of the all-solid-state secondary battery of Reference Example 1 were inferior to those of the all-solid-state secondary battery of Example 9.

[0273] As described above, the all-solid-state secondary battery according to this embodiment can be applied to various portable devices, vehicles, and the like.

[0274] Although an exemplary embodiment has been described in detail with reference to the attached drawings, the concept of the present invention is not limited to such an example. It is obvious that a person having ordinary skill in the art to which the concept of the present invention pertains can derive various modified or altered examples within the scope of the technical concept described in the claims, and it goes without saying that these also belong to the technical scope of the concept of the present invention. [Explanation of symbols]

[0275] 1 All-solid-state secondary battery 10 Positive electrode layer 11 Positive electrode current collector 12 Cathode active material layer 20 Negative electrode layer 21 Negative electrode current collector 22 First negative electrode active material layer 30 Solid electrolyte layer 40 First Inactive Material 50 Second inert material

Claims

1. a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer; the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer disposed on one or both sides of the positive electrode current collector, The positive electrode active material layer includes a lithium-containing sulfide-based positive electrode active material, and the lithium-containing sulfide-based positive electrode active material is Li 2 S., Li. 2 S-containing complexes or combinations thereof, a first inactive member disposed on one side of the positive electrode layer; the negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer disposed on one surface of the negative electrode current collector, a ratio (B / A) of an initial charge capacity (B) of the first negative electrode active material layer to an initial charge capacity (A) of the positive electrode active material layer is 0.005 to 0.45; The initial charge capacity of the positive electrode active material layer is calculated from the first open circuit voltage as follows: Li / Li + is determined by charging to the maximum charging voltage, The initial charge capacity of the first negative electrode active material layer is calculated from the second open circuit voltage as follows: Li / Li + An all-solid-state secondary battery, as determined by charging to 0.01 V relative to the battery.

2. The Li 2 The S-containing complex is Li 2 A composite of S and a conductive material, Li 2 A composite of S, a solid electrolyte, and a conductive material, Li 2 S and solid electrolyte composite, Li 2 A composite of S, a lithium salt, and a conductive material, Li 2 A complex of S and a lithium salt, Li 2 S and metal carbide complex, Li 2 A composite of S, a metal carbide and a conductive material, Li 2 S and metal nitride complex, Li 2 2. The all-solid-state secondary battery of claim 1, comprising a composite of S, a metal nitride, and a conductive material, or a combination thereof.

3. Li 2 The S-containing complex is Li 2 A complex of S and a lithium salt, Li 2 A composite of S, a lithium salt, and a conductive material, Li 2 Complex of S and metal halide, Li 2 A composite of S, a metal halide and a conductive material, Li 2 A complex of S, a lithium salt and a metal halide, Li 2 A complex of S, a lithium salt, a metal halide, and a conductive material, or a combination thereof; The Li 2 The complex of S and lithium salt is Li 2 S-Li a X1 b (1≦a≦5, 1≦b≦5), The Li 2 The composite of S, a lithium salt, and a conductive material is Li 2 S-Li a X1 b -C (1≦a≦5, 1≦b≦5), The Li 2 The complex of S and metal halide is Li 2 S-M c X2 d (1≦c≦5, 1≦d≦5), The Li 2 The composite of S, metal halide and conductive material is Li 2 S-M c X2 d -C (1≦c≦5, 1≦d≦5) The Li 2 A complex of S, a lithium salt, and a metal halide is Li 2 S-Li a X1 b -M c X2 d (1≦a≦5, 1≦b≦5, 1≦c≦5, 1≦d≦5), The Li 2 A complex of S, a lithium salt, a metal halide, and a conductive material is Li 2 S-Li a X1 b -M c X2 d -C (1≦a≦5, 1≦b≦5, 1≦c≦5, 1≦d≦5), The X1 is I, Br, Cl, F, H, O, Se, Te, N, P, As, Sb, Al, B, OCl, PF 6 , B.F. 4 , SbF 6 , AsF 6 , ClO 4 , AlO 2 , AlCl 4 , NO 3 , CO 3 , B.H. 4 , S.O. 4 , B.O. 3 , P.O. 4 , NCl, NCl 2 , B.N. 2 or a combination thereof, M is one or more metals selected from Groups 2 to 15 of the Periodic Table; The all-solid-state secondary battery according to claim 1 , wherein X2 is I, Br, Cl, F, or a combination thereof.

4. The Li 2 The S-containing complex is Li 2 Solid solution of S and lithium salt, Li 2 Solid solution of S and metal halide, Li 2 4. The all-solid-state secondary battery according to claim 3, comprising a solid solution of S, a lithium salt, and a metal halide, or a combination thereof.

5. The lithium salt is a binary compound or a ternary compound, The binary compounds are LiI, LiBr, LiCl, LiF, LiH, Li 2 O., Li 2 Se, Li 2 Te, Li 3 N., Li 3 P, Li 3 As, Li 3 Sb, Li 3 A 2 , LiB 3 or any combination thereof, The ternary compound is Li 3 OCl, LiPF 6 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiClO 4 , LiAlO 2 , LiAlCl 4 , LiNO 3 , Li 2 CO 3 , LiBH 4 , Li 2 SO 4 , Li 3 B.O. 3 , Li 3 P.O. 4 , Li 4 NCl, Li 5 NCl 2 , Li 3 BN 2 Or a combination thereof. The all-solid-state secondary battery according to claim 3 .

6. The metal halide comprises one or more metals selected from Al, Mg, Ti, Sn, As, Sb, Nb, Sc, Zr, V, W, Mn, Fe, Co, Pd, Cu, Ag, Zn, and Se; The metal halide is AlF 3 , AlCl 3 , AlBr 3 , ALI 3 , MgF 2 , MgCl 2 , MgBr 2 , MgI 2 , TiF 4 , TiCl 4 , TiBr 4 , TiI 4 , SnF 4 , SnCl 4 , SnBr 4 , SnI 4 , AsF 4 , AsCl 4 , AsBr 4 , AsI 4 , SbF 4 , SbCl 4 , SbBr 4 , SbI 4 or a combination thereof.

7. The Li 2 The S-containing complex is Li 2 A composite of S, a lithium salt, a metal halide, and a conductive material, The Li 2 Li for 100 parts by weight of a composite of S, a lithium salt, a metal halide, and a conductive material 2 S 40 to 80 parts by weight, a combination of a lithium salt and a metal halide 1 to 40 parts by weight, and a conductive material 1 to 20 parts by weight, the molar ratio of the lithium salt to the metal halide is 3:1 to 1:3; In the positive electrode active material layer, 2 The all-solid-state secondary battery according to claim 1 , wherein the S content is 40 wt % or more.

8. the first inactive member surrounds a side surface of the positive electrode layer and is in contact with the solid electrolyte layer; the first inactive member extends from one side of the positive electrode layer along a surface of the solid electrolyte layer to an end portion of the solid electrolyte layer; the area of ​​the positive electrode layer is smaller than the area of ​​the solid electrolyte layer in contact with the positive electrode layer, the first inactive member surrounds a side surface of the positive electrode layer and compensates for an area difference between the positive electrode layer and the solid electrolyte layer; the thickness of the first inactive member is greater than the thickness of the first negative electrode active material layer, the thickness of the first negative electrode active material layer is 50% or less of the thickness of the first inactive member, The all-solid-state secondary battery according to claim 1 , wherein no negative electrode active material layer is present on the other surface of the negative electrode current collector.

9. the first inert member comprises a flame-retardant inert member, the flame-retardant inert member comprises a matrix and a filler; the matrix comprises a substrate and a reinforcing material; The substrate includes a first fibrous material, the first fibrous material is an insulating material, and the first fibrous material includes one or more selected from the group consisting of pulp fibers, insulating polymer fibers, and ion-conducting polymer fibers; The reinforcing material includes a second fibrous material, the second fibrous material being a flame retardant material, and the second fibrous material includes one or more selected from glass fibers and ceramic fibers; the filler is a moisture adsorbent, the filler comprising a metal hydroxide; The metal hydroxide is Mg(OH). 2 , Fe(OH) 3 , Sb(OH) 3 , Sn(OH) 4 , TI(OH) 3 , Zr(OH) 4 , and Al(OH) 3 The all-solid-state secondary battery according to claim 1 , comprising one or more selected from the following:

10. the first negative electrode active material layer includes a negative electrode active material and a binder, 2. The all-solid-state secondary battery according to claim 1, wherein the negative electrode active material is particulate, and the average particle size of the negative electrode active material is 4 μm or less.

11. the negative electrode active material includes at least one selected from the group consisting of a carbon-based negative electrode active material and a metal or semi-metal negative electrode active material; The carbon-based negative electrode active material includes amorphous carbon, crystalline carbon, porous carbon, or a combination thereof; 11. The all-solid-state secondary battery according to claim 10, wherein the metal or semi-metallic negative electrode active material comprises gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), zinc (Zn) or a combination thereof.

12. the negative electrode active material includes a mixture of first particles made of amorphous carbon and second particles made of a metal or semimetal, The all-solid-state secondary battery of claim 10, wherein the content of the second particles is 1 to 60 wt % based on the total weight of the mixture.

13. The all-solid-state secondary battery according to claim 1 , wherein the first negative electrode active material layer further comprises a solid electrolyte.

14. the negative electrode active material includes a carbon-based support and a metal-based negative electrode active material supported on the carbon-based support, the metal-based negative electrode active material comprises a metal, a metal oxide, a composite of a metal and a metal oxide, or a combination thereof; The metal-based negative electrode active material has a particulate shape, and the particle size of the metal-based negative electrode active material is 1 nm to 200 nm; the carbon-based support has a particulate shape, the particle size of the carbon-based support is 10 nm to 2 μm, and the all-solid-state secondary battery further includes a second negative electrode active material layer disposed between the negative electrode current collector and the first negative electrode active material layer after the all-solid-state secondary battery is charged; The all-solid-state secondary battery according to claim 10 , wherein the second negative electrode active material layer is a metal layer, and the metal layer contains lithium or a lithium alloy.

15. The negative electrode current collector further includes a second inactive member disposed on the other surface of the negative electrode current collector, The all-solid-state secondary battery according to claim 1 , wherein the second inactive member comprises a conductive flame-retardant inactive member.

16. the Young's modulus of the second inactive member is smaller than the Young's modulus of the negative electrode current collector, The second inactive member has a Young's modulus of 100 MPa or less, the thickness of the second inactive member is greater than the thickness of the first negative electrode active material layer, The all-solid-state secondary battery according to claim 15 , wherein a thickness of the first negative electrode active material layer is 50% or less of a thickness of the second inactive member.

17. The volume expansion rate of the all-solid-state secondary battery after charging is 15% or less, The all-solid-state secondary battery according to claim 1, wherein the energy density of the all-solid-state secondary battery is 500 to 900 Wh / L or 350 to 600 Wh / kg.

18. the solid electrolyte layer comprises an electrolyte; the electrolyte comprises a solid electrolyte, a gel electrolyte, or a combination thereof; The solid electrolyte includes a sulfide-based solid electrolyte, an oxide-based solid electrolyte, a polymer solid electrolyte, or a combination thereof; The gel electrolyte includes a polymer gel electrolyte, 2. The all-solid-state secondary battery according to claim 1, wherein the solid electrolyte layer is impermeable to lithium polysulfide.

19. The sulfide-based solid electrolyte is Li 2 S-P 2 S 5 , Li 2 S-P 2 S 5 -LiX, X is a halogen element, Li 2 S-P 2 S 5 -Li 2 O., Li 2 S-P 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 - LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S 5 - LiI, Li 2 S-B 2 S 3 , Li 2 S-P 2 S 5 -Z m S n , m and n are positive numbers, Z is one of Ge, Zn, and Ga, Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 P.O. 4 , Li 2 S-SiS 2 -Li p M.O. q , p, q are positive numbers, M is one of P, Si, Ge, B, Al, GaIn, Li 7-x P.S. 6-x C x , 0≦x≦2, Li 7-x P.S. 6-x B x , 0≦x≦2, and Li 7-x P.S. 6-x I x 19. The all-solid-state secondary battery according to claim 18, wherein x is one or more selected from the group consisting of 0≦x≦2.

20. The sulfide-based solid electrolyte is Li 6 P.S. 5 Cl, Li 6 P.S. 5 Br and Li 6 P.S. 5 I is an argyrodite-type solid electrolyte containing one or more selected from The all-solid-state secondary battery according to claim 18, wherein the density of the argyrodite-type solid electrolyte is 1.5 to 2.0 g / cc.

21. At least one of the positive electrode current collector and the negative electrode current collector includes a base film and a metal layer disposed on one or both sides of the base film; the base film comprises a polymer, the polymer comprising polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof; 2. The all-solid-state secondary battery according to claim 1, wherein the metal layer comprises indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof.

Citation Information

Cited By

  • Anode and lithium ion secondary battery including said anode

    JP2026502707A